Soil water depletion intensifies ecosystem vulnerability in China’s drylands - Hongzhou Wang; Fangyue Zhang; Zhaofei Wu; Zunchi Liu; Guizeng Qi; Jing Zhang; Rongqi Tang; Yongshuo H. Fu (Agricultural and Forest Meteorology, 2026)

Differential Roles of Ag and ZnO in the Bactericidal Activity of Ag/ZnO-Hydroxyapatite Nanocomposites against Multidrug-Associated Methicillin-Resistant Staphylococcus aureus - Dong H. Kwon; Azzedine Bensalem; Sophia Fu (Current Microbiology, 2026)

The Effects of Exogenous Glutathione on β-lactam Susceptibility in New Delhi Metallo-β-Lactamase (NDM-1) Producing Klebsiella pneumoniae - Dong H. Kwon; Sophia Fu; Su-Hwan Kwak (Current Microbiology, 2026)

Neonatal Malnutrition Diagnoses Align Differently With Body Composition Outcomes: A Retrospective Cohort Analysis Evaluating 3 Different Growth Standards - Louise Perna; Kera McNelis; Jacqueline Wessel; Stephanie Merlino Barr; Chunyan Liu; Shelley Ehrlich; Jae H. Kim; Ting Ting Fu (Journal of the Academy of Nutrition and Dietetics, 2026)

Source Transition and Health Implication of PM2.5-Bound Metals: Multi-year High-resolution Observation in a Coastal Megacity - Yanjie Lei; Ming Hu; Yuankai Xie; Anja H. Tremper; Yue Liu; Lan Hong; Xin Cheng; Cheng Huang; Qingyan Fu; Jialiang Feng; David C. Green; Longhua Wu; et al. (Atmospheric Environment, 2026)

Corrigendum to ‘Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model’ [Journal of Photochemistry & Photobiology B: Biology Volume 272 (2025) 113276] - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Effects of urban greenbelt on ambient particulate matter under multiple urban stressors and their interactions during heavily polluted winter conditions - D.Y. Hao; H. Liu; J.Z. Song; A. Przybysz; R. Popek; H.J. Yi; J.C. He; Z.C. Fu; C.Y. Zhu (Atmospheric Pollution Research, 2026)

Knockdown of circFOXN3 Promotes the Proliferation and Differentiation of Bovine Myoblasts - Xiangyang Guo; Yi Song; Maryam Alenize; Raha Osailan; Yu Li; Fan Xu; Shubin Fu; Afnan O. Deebani; Aaishah M. H. Kaabi; Zahrah R. Alrayes; Uzma Batool; Gongwei Zhang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Biochar reshapes soil bacterial community composition and survival strategies: a meta-analysis revealing trade-offs between microbial stability and functional complexity - Jianwei Li; Jeewani H. Peduruhewa; Robert W. Brown; David R. Chadwick; Robert I. Griffiths; Haoran Fu; Hongfeng Bian; LianXi Sheng; Qinqxu Ma; Davey L. Jones (Biology and Fertility of Soils, 2026)
As a promising strategy for improving soil health and mitigating climate change, biochar has received increasing attention in recent years. However, findings regarding its microbial effects are often context-dependent, and the complex impacts of biochar on soil microbial communities remain inadequately understood. Here, we integrated 843 samples of 16 S rRNA sequencing data from 24 independent studies, utilizing machine learning and co-occurrence network analysis to evaluate general patterns and mechanisms by which biochar alters bacteria community composition and survival strategies. Overall, biochar significantly increased soil organic C, total N, pH, and reduced bulk density, which in turn affected microbial communities. While biochar addition did not notably alter bacterial α-diversity (Shannon index or species richness), it significantly changed β-diversity, indicating that biochar addition altered microbial community composition. Biochar changed community composition and survival strategies by reducing the oligotroph/copiotroph ratio, favouring copiotrophs groups (e.g., Bacteroidota). K -strategists (e.g., Planctomycetota) were reduced by biochar, potentially due to increased nutrient availability and increased competition. Model selection analysis identified that soil physicochemical properties were key drivers of α-diversity, while climate variables were the main factors influencing β-diversity. Biochar properties represented key factors influencing changes in microbial survival strategy. Machine learning identified 138 biomarker genera, with biochar-treated soils showing an increase in Pseudomonadota. Co-occurrence network analysis indicated that biochar increased microbial stability, but reduced network complexity, suggesting a trade-off between resilience and functional redundancy following biochar addition. These findings provide new insights into how biochar influences the composition and ecological functions of soil bacterial communities and offer theoretical support for its scientific application in sustainable soil management.

Shifting optimal preseason length alters temperature effects on leaf senescence - Zhendong Guo; Zhaofei Wu; Shouzhi Chen; Zitong Jia; Yongshuo H. Fu (Agricultural and Forest Meteorology, 2026)

Apatite cathodoluminescence and trace element geochemistry of Neoarchean and Paleoproterozoic iron oxide-copper-gold (IOCG) deposits of the Carajás domain, Brazil: implications for fluid evolution and metallogenesis - Raphael B. Hunger; Carolina P. N. Moreto; Roberto P. Xavier; Gustavo H. C. de Melo; Lena V. S. Monteiro; Gláucia N. Queiroga; Cristiano de C. Lana; Wang Liao; Xin-Fu Zhao; Poliana I. de F. Toledo (Mineralium Deposita, 2026)

The Increased Effect of Spring Leaf Unfolding on Autumn Senescence in the Northern and Southern Hemispheres - Dong Tang; Shubin Xie; Jie Peng; Ying Sun; Abraham Allan Degen; Yuan Sun; Jiali Luo; Zifan Li; Yaning Kuang; Lixue Wei; Weigang Hu; Longwei Dong; et al. (Global Ecology and Biogeography, 2025)
Aim To investigate the contributions of vegetation growth carryover (VGC, defined as the effect of present states of vegetation growth on subsequent phenophases) and climatic factors to plant phenology, particularly start‐of‐season (SOS) and end‐of‐season (EOS), and how these contributions have evolved globally over the past four decades. Location Global, with a focus on the Northern Hemisphere (NH) and Southern Hemisphere (SH). Time Period 1963–2015 for ground observations, 1982–2022 for satellite NDVI data, and 1982–2022 for climate data (temperature, precipitation, radiation, and potential evapotranspiration). Major Taxa Studied Global vegetation, without specifying individual species. Methods We analysed two sets of satellite‐derived NDVI data, ground‐based phenological observations, and long‐term climate data (temperature, precipitation, radiation, and potential evapotranspiration). Statistical models quantified the contributions of climatic factors and VGC to phenology trends. Results Globally, advanced SOS was driven primarily by increasing temperature and radiation, while delayed EOS was attributed to rising temperature and the carryover effect of spring vegetation growth (VGC SOS ). VGC SOS was the dominant driver of EOS in the SH, whereas temperature played a larger role in the NH. Over the past four decades, the contribution of VGC SOS to EOS has increased significantly on a global scale. However, the SH experienced pronounced “warming and drying” trends, which weakened the relative contribution of VGC SOS to EOS compared to climate‐driven delays. Main Conclusions VGC SOS plays a substantial role in shaping EOS in both hemispheres, with its importance increasing over time. These findings improve our understanding of vegetation dynamics and offer valuable insights for predicting vegetation growth and carbon sequestration under future global warming scenarios.

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

A novel fully coupled thermal-hydraulic-mechanical model for hydrogen storage in depleted gas reservoirs - Jing Fu; Keni Zhang; Hongjun Yin; Philip H. Winterfeld; Yu-Shu Wu (Gas Science and Engineering, 2025)

A direct procedure for the determination of the axis of twist and correlation with shear centers - H. Fu; H.F. Nied (Engineering Structures, 2025)

Increasing impacts of compound extreme droughts on vegetation productivity in China - Guizeng Qi; Jinxi Song; Shouzhi Chen; Yufeng Gong; Hongying Bai; Dunxian She; Jun Xia; Yongshuo H. Fu (Journal of Hydrology, 2025)

P16-05 The zebrafish microbiome has the capacity to bioactivate PFOS precursor compounds - S. Gutsfeld; C. Wray; N. Schweiger; A. Röhrig; H. Paschke; Q. Fu; J. Kasmanas; S. Kader; U. da Rocha; T. Tal (Toxicology Letters, 2025)

A commentary on strategic community-led directions for water quality modelling in Australia and New Zealand - Danlu Guo; Anna Lintern; Alexander H. Elliott; Melanie E. Roberts; Susan M. Cuddy; Ulrike Bende-Michl; Baihua Fu; Klaus Joehnk; Robert Sargent; Danswell Starrs; Anthony J. Jakeman; Vaughn Grey; et al. (Journal of Hydrology, 2025)

Atmospheric and oceanic energy transport during North Atlantic freshening events: influences of moisture transport and hydrologic cycle feedbacks - Seung H. Baek; Juan M. Lora; Christopher B. Skinner; Minmin Fu; Jiang Zhu (Climate Dynamics, 2025)

Removal of fluoroquinolone antibiotic from wastewater based on immobilized metal affinity mechanism - L Zhao; B. Jia; M. He; H. Hu; Y. Guo; G. Fu; C. Hou; S. Gao; R. Li; X. Lv (International Journal of Environmental Science and Technology, 2025)

Rapid degradation of frozen soil environments in thermokarst-affected alpine grasslands on the Qinghai-Tibet Plateau under climate change - Yuanhong Deng; Xiaoyan Li; Chao Yang; Fangzhong Shi; Shaojie Zhao; Sha Zhou; Chiyuan Miao; Ruiqiang Ding; Yongshuo H. Fu; Xiaofan Yang; Zhigang Wang (CATENA, 2025)

Gold nanoparticles mediate suppression of angiogenesis and breast cancer growth via MMP-9/NF-κB/mTOR and PD-L1/PD-1 signaling: integrative in vitro validation and network pharmacology insights - Alaa Elmetwalli; Tarek El-Sewedy; Mervat G. Hassan; Mohamed O. Abdel-Monem; Jihan Hassan; Nadia F. Ismail; Afrah Fatthi Salama; Junjiang Fu; Nasser Mousa; Deema Kamal Sabir; Ola El-Emam; Ghada Hamdy; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Mapping the landscape of bird strike research: insights from a quantitative analysis - H. X. Wang; W. Fu; N. A. Razak; Y. Y. Shi (International Journal of Environmental Science and Technology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Growth Onset Rather Than Photosynthesis Strongly Regulates Autumn Senescence Termination Besides Climate Change - Shuping Ji; Shilong Ren; Yann Vitasse; Constantin M. Zohner; Yongshuo H. Fu; Xiaoqiu Chen; Xiaoyang Zhang; Charlotte Grossiord; Huiying Liu; Matthias Peichl; Dailiang Peng; Shuai An; et al. (Global Ecology and Biogeography, 2025)
Aim Plant senescence largely influences the global carbon cycle by regulating the growing season length. However, the driving mechanisms of plant senescence remain unclear, particularly the role of developmental factors. This study aims to investigate how environmental and developmental factors drive autumn senescence and evaluate whether woody and herbaceous plants exhibit divergent responses to these drivers. Location Eurasia. Time Period 1982–2014. Major Taxa Studied Woody and herbaceous species. Methods Using 120,833 long‐term ground phenological observations, we employed partial correlation analysis to investigate the influence of environmental and developmental factors on senescence termination. Experimental records from literature and pasture survey observations from China were separately utilised to further validate the influence of developmental factors on senescence termination. Structural equation modelling was applied to analyse the pathways of growth onset affecting senescence termination. Additionally, multiple linear regression was used to examine the tendency of the sensitivity of senescence termination to plant development rate. Results We find that earlier growth onset primarily leads to earlier senescence termination directly in herbaceous plants, but indirectly in woody plants by accelerating early‐season development. The sensitivity of senescence termination to plant development rate shows a declining trend, particularly in early‐season negative effects on woody plants and late‐season positive effects on herbaceous plants, suggesting diminished impacts of future warming on senescence timing. The impact of growing season photosynthetic activity on senescence termination is not pronounced for both woody and herbaceous plants. Main Conclusions The results demonstrate that growth onset may affect woody and herbaceous senescence termination through different pathways, whereas the carry‐over effects of growing season photosynthetic activity are not widely discovered. This emphasises that the introduction of developmental factors into phenological models needs to be considered carefully according to plant type.

ApoM-bound S1P acts via endothelial S1PR1 to suppress choroidal neovascularization and vascular leakage - Bongnam Jung; Hitomi Yagi; Andrew Kuo; Tim F. Dorweiler; Masanori Aikawa; Taku Kasai; Sasha A. Singh; Andrew J. Dannenberg; Zhongjie Fu; Colin Niaudet; Lois E. H. Smith; Timothy Hla (Angiogenesis, 2025)

Increasing humification and reducing CH4 emission during rice straw fermentation: the role of Streptomyces rochei ZY-2 - B. Fu; B. Gao; J. Zhang; H. Huang; Z. Wei; Q. Wang; P. Qu (International Journal of Environmental Science and Technology, 2025)

Incorporating Drought Thresholds Improves Model Predictions of Autumn Phenology in Tropical and Subtropical Forests - Yue Xu; Mingwei Li; Zitong Jia; Yufeng Gong; Xiran Li; Yongshuo H. Fu (Global Change Biology, 2025)
Drought dramatically influences vegetation phenology, thereby impacting terrestrial carbon and water cycles. However, the mechanisms by which drought drives changes in autumn phenology remain unclear, hindering the accurate simulation of these processes in phenology models. In this study, we employed ridge regression analysis to quantify the dynamic effects of intensifying drought on the end‐of‐photosynthetic‐growing‐season (EOPS) and identified the drought threshold at which the vegetation's response to drought shifts. We demonstrate that the response of EOPS in tropical and subtropical forests reverses from a delay to an advancement as drought intensity surpasses specific thresholds, with the average drought threshold across the study area corresponding to a standardized precipitation evapotranspiration index (SPEI) value of −0.9. Drought thresholds, however, vary geographically, increasing along the precipitation gradient, potentially due to variations in drought stress‐related gene expression and tolerance strategies across different humidity environments. Therefore, we developed a new autumn phenology model (DMPD) by incorporating a drought threshold parameter that distinguishes contrasting drought effects and predicts future EOPS under two scenarios (SSP245 and SSP585). The DMPD model substantially enhanced the representation of EOPS, as evidenced by a lower root mean square error (RMSE), higher correlation, and a greater proportion of significant correlations with EOPS derived from GOSIF. By the end of the century, EOPS is projected to be consistently delayed under both moderate (SSP245) and high (SSP585) warming scenarios, with the rate of delay decelerating under SSP245 after 2066. Our study confirms that increasing drought intensity leads to contrasting shifts in the autumnal photosynthetic phenology of tropical and subtropical forests and highlights the potential of integrating these contrasting drought effects into phenology models to improve the accuracy of vegetation phenology predictions under future climate change scenarios.

Increased Growth Temperatures Alter Arctic Plant Responses to Heat Wave and Drought - Marta Contreras‐Serrano; Neel Lindsby; Riikka Rinnan; Emma C. N. Duegaard; Eva Rosenqvist; Shouzhi Chen; Yongshuo H. Fu; Jing Tang (Global Change Biology, 2025)
Persistent warming and higher frequency of heat waves in the Arctic are causing alterations in Arctic vegetation and plant functionality, potentially redefining the role of the Arctic ecosystem. Vegetation influences atmospheric composition through exchanges of CO 2 and volatile organic compounds (VOCs), both processes exhibiting a strong response to temperature variations. However, our quantitative understanding of how increased temperatures interact with extreme weather events, namely heat waves and drought, to affect Arctic plant processes remains limited. Here, we measure phenology, photosynthesis, leaf fluorescence and VOC emissions from three widely distributed Arctic shrubs, Betula nana , Empetrum hermaphroditum and Salix spp., in response to future climate. We use state‐of‐the‐art climate chambers to test the effects of warmer growth temperatures on Arctic shrub responses to heat waves and drought. Our results show that increased growth temperatures advance leaf unfolding by 24 days in B. nana and 17 days in E. hermaphroditum , and increase VOC emissions across species. For B. nana , photosynthesis decreased by 42% during the heat wave and by 72% during drought. In contrast, Salix spp. and E. hermaphroditum experienced decreased photosynthesis only during drought, by 62% and 71%, respectively. The VOC emissions during the heat wave shifted toward a less diverse compound profile: acetaldehyde emissions increased for both control and warmed plants in all species, and isoprene emissions increased in Salix spp. Additionally, plants grown at higher temperatures exhibited a twofold increase in emissions compared to control plants during the heat wave, suggesting a higher temperature sensitivity of emissions. Our study indicates that warming and increasingly frequent extreme weather events will significantly impact Arctic plant phenology, photosynthesis and the diversity and rates of VOCs emitted into the atmosphere, contributing to modifying the regional climate.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Attributions of Rainfall Anomalies to Weather Systems and Their Spatial and Temporal Variabilities: A Case Study of Victoria in Southeast Australia - Guobin Fu; Francis H. S. Chiew; David A. Post; Acacia Pepler; Irina Rudeva (International Journal of Climatology, 2024)
Attributions of rainfall anomalies to weather systems and their spatio‐temporal variability in Victoria, southeast Australia are investigated with a multimethod weather type dataset and two popularly used gridded daily rainfall datasets for the period 1979–2015. The rainfall anomalies before, during and after the Millennium Drought (1997–2009) are compared to quantify the temporal variability of rainfall responses to weather type changes. The results show: (1) Three weather systems (Front, Cyclone and Thunderstorm) and their combinations contribute 89% of total rainfall; (2) Contributions of weather types to rainfall vary from month to month with winter season rainfall coming from more diverse weather types than summer rainfall; (3) The contributions of weather types to rainfall in three periods show temporal variabilities and there is a clear shift of contribution pattern after the Millennium Drought, such as front‐thunderstorm (FT) is now the largest contributor to rainfall compared with cyclone‐frontal‐thunderstorm (CFT) before and during the Millennium Drought; (4) A seasonal shift in the post‐drought period is found with higher rainfall in February and March and lower rainfall in September and October. The increased rainfall in February mainly results from Front–Thunderstorm (FT) and Thunderstorm‐only (TO), while rainfall declines in September from all weather types; (5) Several rainfall characteristics that are important for streamflow generation, such as rainfall intensity, probability of rainfall occurrence, number of rainfall days and the maximum daily rainfall, do depend on the weather types; (6) The results are similar with different rainfall datasets, but differences do exist, especially at the local scale. The conclusions of this study are drawn from an Australian case study but have implications for other regions to investigate the attributions of rainfall characteristic changes to weather systems.

Chemical classification of spherules recovered from the Pacific Ocean site of the CNEOS 2014-01-08 (IM1) bolide - A. Loeb; S.B. Jacobsen; R. Tagle; T. Adamson; S. Bergstrom; J. Cherston; R. Cloete; S. Cohen; L. Domine; H. Fu; C. Hoskinson; E. Hyung; et al. (Chemical Geology, 2024)

Correction: Mitochondrial control of hypoxia-induced pathological retinal angiogenesis - Hitomi Yagi; Myriam Boeck; Shen Nian; Katherine Neilsen; Chaomei Wang; Jeff Lee; Yan Zeng; Matthew Grumbine; Ian R. Sweet; Taku Kasai; Kazuno Negishi; Sasha A. Singh; et al. (Angiogenesis, 2024)

Mitochondrial control of hypoxia-induced pathological retinal angiogenesis - Hitomi Yagi; Myriam Boeck; Shen Nian; Katherine Neilsen; Chaomei Wang; Jeff Lee; Yan Zeng; Matthew Grumbine; Ian R. Sweet; Taku Kasai; Kazuno Negishi; Sasha A. Singh; et al. (Angiogenesis, 2024)
Objective Pathological retinal neovascularization is vision-threatening. In mouse oxygen-induced retinopathy (OIR) we sought to define mitochondrial respiration changes longitudinally during hyperoxia-induced vessel loss and hypoxia-induced neovascularization, and to test interventions addressing those changes to prevent neovascularization. Methods OIR was induced in C57BL/6J mice and retinal vasculature was examined at maximum neovessel formation. We assessed total proteome changes and the ratio of mitochondrial to nuclear DNA copy numbers (mtDNA/nDNA) of OIR vs. control retinas, and mitochondrial oxygen consumption rates (OCR) in ex vivo OIR vs. control retinas (BaroFuse). Pyruvate vs. vehicle control was supplemented to OIR mice either prior to or during neovessel formation. Results In OIR vs. control retinas, global proteomics showed decreased retinal mitochondrial respiration at peak neovascularization. OCR and mtDNA/nDNA were also decreased at peak neovascularization suggesting impaired mitochondrial respiration. In vivo pyruvate administration during but not prior to neovessel formation (in line with mitochondrial activity time course) suppressed NV. Conclusions Mitochondrial energetics were suppressed during retinal NV in OIR. Appropriately timed supplementation of pyruvate may be a novel approach in neovascular retinal diseases.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Genesis of Pb–Zn-Ag-Sb mineralization in the Tethys Himalaya, China: Early magmatic-hydrothermal Pb–Zn(-Ag) mineralization overprinted by Sb-rich fluids - Xiang Sun; Ru-Yue Li; Hao-Yu Sun; Paul H. Olin; M. Santosh; Bin Fu; Jun Deng (Mineralium Deposita, 2024)

P10-08 Evaluation of real-life PFAS mixture toxicity and impact on 3D placenta spheroid model - Y. Xia; Q. Fu; H. Voss; S. Fest; A.C. Zenclussen; V. Stojanovska (Toxicology Letters, 2024)

Inefficient burial of terrestrial organic carbon in deltas - Yonggui Yu; Jaap H. Nienhuis; Zhengquan Yao; Marcel van der Perk; Bin Zhao; Shuqing Qiao; Xuefa Shi; Gabriel Cardenas-Belleza; Sheng Fu; Francien Peterse; Yazhi Bai; Hans Middelkoop (Earth and Planetary Science Letters, 2024)

Correction: Histamine induces the production of matrix metalloproteinase-9 in human astrocytic cultures via H1-receptor subtype - Aarti Patel; Vishnu Vasanthan; Wen Fu; Richard P. Fahlman; David MacTavish; Jack H. Jhamandas (Brain Structure and Function, 2024)

Surface soil moisture from combined active and passive microwave observations: Integrating ASCAT and SMAP observations based on machine learning approaches - Hongliang Ma; Jiangyuan Zeng; Xiang Zhang; Jian Peng; Xiaojun Li; Peng Fu; Michael H. Cosh; Husi Letu; Shaohua Wang; Nengcheng Chen; Jean-Pierre Wigneron (Remote Sensing of Environment, 2024)

Corrigendum to “Technological challenges and future perspectives of plant-based meat analogues: From the viewpoint of proteins” [Food Res. Int. 186 (2024) 114351] - Tianyu Su; Bei Le; Wei Zhang; Kathrine H. Bak; Philip O. Soladoye; Zhongquan Zhao; Yongju Zhao; Yu Fu; Wei Wu (Food Research International, 2024)

Improving maize yield estimation by assimilating UAV-based LAI into WOFOST model - Yahui Guo; Fanghua Hao; Xuan Zhang; Yuhong He; Yongshuo H. Fu (Field Crops Research, 2024)

Technological challenges and future perspectives of plant-based meat analogues: From the viewpoint of proteins - Tianyu Su; Bei Le; Wei Zhang; Kathrine H. Bak; Philip O. Soladoye; Zhongquan Zhao; Yongju Zhao; Yu Fu; Wei Wu (Food Research International, 2024)

Elucidating the Correlation of Lignocellulosic Compositions and Physicochemical Alterations in Oil Palm (Elaeis guineensis) Biomass on Enzymatic Saccharification Yield - Tannimalay Hemashini; Chee Keong Lee; Choon Fu Goh; Ying Ying Tye; Maya Ismayati; Yin Ying H’ng; Cheu Peng Leh (BioEnergy Research, 2024)

Addition of iron does not ameliorate sulfide toxicity by sargassum influx to mangroves but dampens methane and nitrous oxide emissions - Sara P. Cobacho; Luuk H. Leemans; Stefan T.J. Weideveld; Xitong Fu; Marieke M. van Katwijk; Leon P.M. Lamers; Alfons J.P. Smolders; Marjolijn J.A. Christianen (Marine Pollution Bulletin, 2024)

Existing levels of biodiversity and river location may determine changes from small hydropower developments - Qingyi Luo; Shuyin Li; Tsuyoshi Kinouchi; Naicheng Wu; Xiaocheng Fu; Chang Ling; Qinghua Cai; Ming-Chih Chiu; Vincent H. Resh (Journal of Environmental Management, 2024)

Iron oxide–apatite deposits form from hydrosaline liquids exsolved from subvolcanic intrusions - Xin-Fu Zhao; Li-Ping Zeng; Wang Liao; Yi-Zhe Fan; Albert H. Hofstra; Poul Emsbo; Hao Hu; Guang Wen; Jian-Wei Li (Mineralium Deposita, 2024)

Diurnal variation in short‐ and long‐duration precipitation within the Dabie Mountain region in Central China - Chao Li; Chunguang Cui; Xingwen Jiang; Xiaofang Wang; Shenming Fu; Wenjun Cui; Andrew H. Berrington; Jing Sun; Peiting Liu (International Journal of Climatology, 2024)
Diurnal variation in regional precipitation in Central and East China has been broadly identified in previous study. This study focused on clarifying not only the differences in the diurnal variation concerning the local precipitation occurred in the Dabie Mountain (DBM) region and the regional precipitation occurred through the middle‐lower reaches of the Yangtze River Basin, but also the association mechanism between diurnal variation in local precipitation with differing duration and diurnal modulation of ambient circulations driven by large‐scale background synoptic force or local‐scale orographic force of the DBM. It was found that cases of short duration precipitation (SDP, duration

Substantial increase of heat requirement for maturity of early rice due to extension of reproductive rather vegetative growth period in China - Yaru Zhang; Yahui Guo; Shuxin Wang; Wenxiang Wu; Yongshuo H. Fu (Theoretical and Applied Climatology, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Genetics and metabolic responses of Artemisia annua L to the lake of phosphorus under the sparingly soluble phosphorus fertilizer: evidence from transcriptomics analysis - Lingyun Wan; Juan Huo; Qiulan Huang; Xiaowen Ji; Lisha Song; Zhanjiang Zhang; Limei Pan; Jine Fu; Mohamed A. Abd Elhamid; Salma A. Soaud; Rania M. Y. Heakel; Jihai Gao; et al. (Functional & Integrative Genomics, 2024)

Urbanization effects on the spatial patterns of spring vegetation phenology depend on the climatic background - Peiyi Yin; Xuecao Li; Yuyu Zhou; Jiafu Mao; Yongshuo H. Fu; Wenting Cao; Peng Gong; Wanru He; Baoguo Li; Jianxi Huang; Xiaoping Liu; Zitong Shi; et al. (Agricultural and Forest Meteorology, 2024)

Functions and values of sulfated polysaccharides from seaweed - D. P. Nagahawatta; N. M. Liyanage; Thilina U. Jayawardena; Fengqi Yang; H. H. A. C. K. Jayawardena; M. J. M. S. Kurera; Fahe Wang; Xiaoting Fu; You-Jin Jeon (Algae, 2023)
Sulfated polysaccharides (SPs) isolated from seaweed have emerged as remarkable bioactive compounds with a wide spectrum of biological activities and have substantial value in the scientific and industrial domains. The current study explores the diverse biological activities of SPs and their relationship with their structures. This aids in an in-depth examination of the multifaceted biological activities of SPs, including anticoagulant, anti-inflammatory, antiviral, antioxidant, and immunomodulatory properties, which underpin their potential health benefits. Furthermore, the current study explores the complicated properties of SPs, with their extraction methodologies and techniques for precise characterization. Elucidation of the commercial significance of SPs derived from brown, red, and green seaweed by highlighting their potential applications has emphasized their importance in human well-being. Further, this review emphasizes the challenges needed to overcome research and industrial innovations for SPs. Collaboration among researchers, industry stakeholders, and regulatory authorities can overcome these challenges and elevate the potential of SPs to revolutionize industries such as pharmaceuticals, cosmeceuticals, food, and biotechnology.

16s-RNA sequencing analysis of the influence of UV radiation on the metabolic pathways of pollutants in the A2O process - Y. W. Li; J. H. You; Y. C. Zong; J. Wang; C. H. Fu (International Journal of Environmental Science and Technology, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Evidence of advancing spring xylem phenology in Chinese forests under global warming - Huihong Xue; Feng Shi; Fabio Gennaretti; Yongshuo H. Fu; Bin He; Xiuchen Wu; Zhengtang Guo (Science China Earth Sciences, 2023)

Petrogenesis and tectonic implications of the early Paleozoic granites in the Lincang granitic batholith, southwestern China: Constraints from geochronology, geochemistry and Hf isotopes - Qian R. Xiao; Qiang Wang; Zhong Y. Liu; Fu H. Xiong; Lei Fan; Han Zhao; Ting T. Gong (Ore and Energy Resource Geology, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Cerebrospinal fluid levels of 5-HIAA and dopamine in people with HIV and depression - Rong Fu; Hyder Jinnah; J. Lucas Mckay; Andrew H. Miller; Jennifer C. Felger; Eugene W. Farber; Sanjay Sharma; Neil Whicker; Raeanne C. Moore; Donald Franklin; Scott L. Letendre; Albert M. Anderson (Journal of NeuroVirology, 2023)

FGF21 via mitochondrial lipid oxidation promotes physiological vascularization in a mouse model of Phase I ROP - Zhongjie Fu; Pia Lundgren; Aldina Pivodic; Hitomi Yagi; Jarrod C. Harman; Jay Yang; Minji Ko; Katherine Neilsen; Saswata Talukdar; Ann Hellström; Lois E. H. Smith (Angiogenesis, 2023)
Hyperglycemia in early postnatal life of preterm infants with incompletely vascularized retinas is associated with increased risk of potentially blinding neovascular retinopathy of prematurity (ROP). Neovascular ROP (Phase II ROP) is a compensatory but ultimately pathological response to the suppression of physiological postnatal retinal vascular development (Phase I ROP). Hyperglycemia in neonatal mice which suppresses physiological retinal vascular growth is associated with decreased expression of systemic and retinal fibroblast growth factor 21 (FGF21). FGF21 administration promoted and FGF21 deficiency suppressed the physiological retinal vessel growth. FGF21 increased serum adiponectin (APN) levels and loss of APN abolished FGF21 promotion of physiological retinal vascular development. Blocking mitochondrial fatty acid oxidation also abolished FGF21 protection against delayed physiological retinal vessel growth. Clinically, preterm infants developing severe neovascular ROP (versus non-severe ROP) had a lower total lipid intake with more parenteral and less enteral during the first 4 weeks of life. Our data suggest that increasing FGF21 levels in the presence of adequate enteral lipids may help prevent Phase I retinopathy (and therefore prevent neovascular disease).

Scale avoidance during waterflooding by optimized effluent mixing - Peter Birkle; Yunjiao Fu; Anaam H. Al-ShaikhAli; Shouwen Shen (Arabian Journal of Geosciences, 2023)

Causal relations between the loop current penetration and the inflow/outflow conditions inferred with a rigorous quantitative causality analysis - Yang Yang; Guanqi Fu; X. San Liang; Robert H. Weisberg; Yonggang Liu (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

RNA sequencing in Artemisia annua L explored the genetic and metabolic responses to hardly soluble aluminum phosphate treatment - Lingyun Wan; Qiulan Huang; Xiaowen Ji; Lisha Song; Zhanjiang Zhang; Limei Pan; Jine Fu; Rania G. Elbaiomy; Ahmed S. Eldomiaty; Shabir A. Rather; Mohamed M. A. Elashtokhy; Jihai Gao; et al. (Functional & Integrative Genomics, 2023)

Transcriptome Analysis Reveals Key Molecular Pathways in Response to Alkaline Salt Stress in Canola (Brassica napus L.) Roots - Weichao Wang; Jiayin Pang; Fenghua Zhang; Lupeng Sun; Lei Yang; Tingdong Fu; Kadambot H. M. Siddique (Journal of Plant Growth Regulation, 2023)

Preparation of carbonaceous adsorption composite with refinery sludge for butyl xanthate and diethyldithiocarbamate removal in flotation wastewater - P. Fu; H. Yang; Q. Zhang; X. Li (International Journal of Environmental Science and Technology, 2023)

Photoperiod drives cessation of wood formation in northern conifers - Wenhuan Mu; Xiuchen Wu; J. Julio Camarero; Yongshuo H. Fu; Jianguo Huang; Xiaoyan Li; Deliang Chen (Global Ecology and Biogeography, 2023)
Aims Shifts in xylem phenology directly determine the forest capacity for carbon sequestration. However, a systematic understanding of the spatial patterns and the underpinning drivers in determining the cessation of wood formation ( C cw ) is lacking at a pan‐continental scale. Here, we addressed this knowledge gap by compiling a new dataset of multiple xylem phenology timings for northern conifers. Locations Sixty‐two study sites, Northern Hemisphere (25–55° N). Time period 2003–2018 (16 years). Taxa Thirty‐three conifer species. Methods A generalized additive model was fitted to characterize the latitudinal pattern in C cw . Structural equation modelling and a linear mixed‐effects model were applied to determine the main drivers underlying the latitudinal pattern in C cw . Results The C cw followed a flat S‐shaped pattern with increasing latitude. Photoperiod was the dominant determinant of the latitudinal pattern of C cw , and a longer photoperiod was associated with an earlier C cw . Both mean growing‐season temperature and total growing‐season precipitation exhibited significantly positive relationships to the cessation of cell elongation and thus the C cw across all study sites. In arid regions, the pre‐growing‐season temperature had a significantly negative effect on C cw . In humid regions, C cw was positively affected by the mean growing‐season temperature. The onset of wood formation showed significantly positive coupling with C cw at arid sites but not at humid sites. Early successional species were sensitive to hydrothermal variations during the pre‐growing season. Main conclusions We reveal the dominant role of photoperiod in determining the cessation of wood formation for northern conifers and highlight differentiated interactive effects between photoperiod and seasonal climatic factors and the preceding xylem phenophases in determining C cw among ecoregions and tree species. These insights provide evidence to reduce uncertainty in prediction of the forest carbon uptake potential and the consequent biophysical feedbacks of northern forests.

Extended seasonal prediction of spring precipitation over the Upper Colorado River Basin - Siyu Zhao; Rong Fu; Michael L. Anderson; Sudip Chakraborty; Jonathan H. Jiang; Hui Su; Yu Gu (Climate Dynamics, 2023)
This study provides extended seasonal predictions for the Upper Colorado River Basin (UCRB) precipitation in boreal spring using an artificial neural network (ANN) model and a stepwise linear regression model, respectively. Sea surface temperature (SST) predictors are developed taking advantage of the correlation between the precipitation and SST over three ocean basins. The extratropical North Pacific has a higher correlation with the UCRB spring precipitation than the tropical Pacific and North Atlantic. For the ANN model, the Pearson correlation coefficient between the observed and predicted precipitation exceeds 0.45 ( p -value < 0.01) for a lead time of 12 months. The mean absolute percentage error (MAPE) is below 20% and the Heidke skill score (HSS) is above 50%. Such long-lead prediction skill is probably due to the UCRB soil moisture bridging the SST and precipitation. The stepwise linear regression model shows similar prediction skills to those of ANN. Both models show prediction skills superior to those of an autoregression model (correlation < 0.10) that represents the baseline prediction skill and those of three of the North American Multi-Model Ensemble (NMME) forecast models. The three NMME models exhibit different skills in predicting the precipitation, with the best skills of the correlation ~ 0.40, MAPE < 25%, and HSS > 40% for lead times less than 8 months. This study highlights the advantage of oceanic climate signals in extended seasonal predictions for the UCRB spring precipitation and supports the improvement of the UCRB streamflow prediction and related water resource decisions.

Global warming is increasing the discrepancy between green (actual) and thermal (potential) seasons of temperate trees - Yongshuo H. Fu; Xiaojun Geng; Shouzhi Chen; Hao Wu; Fanghua Hao; Xuan Zhang; Zhaofei Wu; Jing Zhang; Jing Tang; Yann Vitasse; Constantin M. Zohner; Ivan Janssens; et al. (Global Change Biology, 2023)
Over the past decades, global warming has led to a lengthening of the time window during which temperatures remain favorable for carbon assimilation and tree growth, resulting in a lengthening of the green season. The extent to which forest green seasons have tracked the lengthening of this favorable period under climate warming, however, has not been quantified to date. Here, we used remote sensing data and long‐term ground observations of leaf‐out and coloration for six dominant species of European trees at 1773 sites, for a total of 6060 species–site combinations, during 1980–2016 and found that actual green season extensions (GS: 3.1 ± 0.1 day decade −1 ) lag four times behind extensions of the potential thermal season (TS: 12.6 ± 0.1 day decade −1 ). Similar but less pronounced differences were obtained using satellite‐derived vegetation phenology observations, that is, a lengthening of 4.4 ± 0.13 and 7.5 ± 0.13 day decade −1 for GS and TS, respectively. This difference was mainly driven by the larger advance in the onset of the thermal season compared to the actual advance of leaf‐out dates (spring mismatch: 7.2 ± 0.1 day decade −1 ), but to a less extent caused by a phenological mismatch between GS and TS in autumn (2.4 ± 0.1 day decade −1 ). Our results showed that forest trees do not linearly track the new thermal window extension, indicating more complex interactions between winter and spring temperatures and photoperiod and a justification of demonstrating that using more sophisticated models that include the influence of chilling and photoperiod is needed to accurately predict spring phenological changes under warmer climate. They urge caution if such mechanisms are omitted to predict, for example, how vegetative health and growth, species distribution and crop yields will change in the future.

Measurements of cerebral microvascular blood flow, oxygenation, and morphology in a mouse model of whole-brain irradiation-induced cognitive impairment by two-photon microscopy and optical coherence tomography: evidence for microvascular injury in the cerebral white matter - Baoqiang Li; Andriy Yabluchanskiy; Stefano Tarantini; Srinivasa Rao Allu; Ikbal Şencan-Eğilmez; Ji Leng; Mohammed Ali H. Alfadhel; Jason E. Porter; Buyin Fu; Chongzhao Ran; Sefik Evren Erdener; David A. Boas; et al. (GeroScience, 2023)

Natural bioactive compounds-doxorubicin combinations targeting topoisomerase II-alpha: Anticancer efficacy and safety - Ahmed Elfadadny; Rokaia F. Ragab; Rania Hamada; Soad K. Al Jaouni; Junjiang Fu; Shaker A. Mousa; Ali H. El-Far (Toxicology and Applied Pharmacology, 2023)

Factors influencing the transfer and abundance of antibiotic resistance genes in livestock environments in China - Z. F. Wang; H. Yun; S. Li; J. Ji; A. Khan; X. L. Fu; P. Zhang; X. K. Li (International Journal of Environmental Science and Technology, 2023)

Radiation‐constrained boundaries cause nonuniform responses of the carbon uptake phenology to climatic warming in the Northern Hemisphere - Adrià Descals; Aleixandre Verger; Gaofei Yin; Iolanda Filella; Yongshuo H. Fu; Shilong Piao; Ivan A. Janssens; Josep Peñuelas (Global Change Biology, 2023)
Climatic warming has lengthened the photosynthetically active season in recent decades, thus affecting the functioning and biogeochemistry of ecosystems, the global carbon cycle and climate. Temperature response of carbon uptake phenology varies spatially and temporally, even within species, and daily total intensity of radiation may play a role. We empirically modelled the thresholds of temperature and radiation under which daily carbon uptake is constrained in the temperate and cold regions of the Northern Hemisphere, which include temperate forests, boreal forests, alpine and tundra biomes. The two‐dimensionality of the temperature‐radiation constraint was reduced to one single variable, θ , which represents the angle in a polar coordinate system for the temperature‐radiation observations during the start and end of the growing season. We found that radiation will constrain the trend towards longer growing seasons with future warming but differently during the start and end of season and depending on the biome type and region. We revealed that radiation is a major factor limiting photosynthetic activity that constrains the phenology response to temperature during the end‐of‐season. In contrast, the start of the carbon uptake is overall highly sensitive to temperature but not constrained by radiation at the hemispheric scale. This study thus revealed that while at the end‐of‐season the phenology response to warming is constrained at the hemispheric scale, at the start‐of‐season the advance of spring onset may continue, even if it is at a slower pace.

Carboniferous mafic-ultramafic intrusions in the Eastern Pontides (Pulur Complex): Implications for the source of coeval voluminous granites - Gültekin Topuz; Rainer Altherr; Osman Candan; Jia-Min Wang; Aral I. Okay; Fu-Yuan Wu; Ali Ergen; Thomas Zack; Wolfgang Siebel; Cosmas K. Shangh; Winfried H. Schwarz; Hans-Peter Meyer; et al. (Lithos, 2023)

Informing the SWAT model with remote sensing detected vegetation phenology for improved modeling of ecohydrological processes - Shouzhi Chen; Yongshuo H. Fu; Zhaofei Wu; Fanghua Hao; Zengchao Hao; Yahui Guo; Xiaojun Geng; Xiaoyan Li; Xuan Zhang; Jing Tang; Vijay P. Singh; Xuesong Zhang (Journal of Hydrology, 2023)

Cymbopogom Citratus Essential Oils: A Promising Source of Antifungals Against Panax Notoginseng-Associated Pathogenic Fungi - Jing Yang; Tian T. Li; Ying Y. Huo; Heng Y. Huang; Qing H. Meng; Fu R. Xu; Xian Dong (Current Microbiology, 2023)

Testing machine learning algorithms on a binary classification phenological model - Wujun Dai; Huiying Jin; Lin Zhou; Tong Liu; Yuhong Zhang; Zhiqiang Zhou; Yongshuo H. Fu; Guangze Jin (Global Ecology and Biogeography, 2023)
Aim Phenological models have become a vital tool for predicting future phenological responses to global climate change. Recently, machine learning (ML) has been used successfully to develop phenological models based on ground observations. However, fitting an observation series that has been observed for only a few years (or even a decade) can easily lead to overfitting, and it is still a great challenge to predict future phenology accurately based on a short observation series. Here, based on historical ground phenological observations, we construct an ML‐based binary classification phenological model that can be applied to temperate trees. Innovation We thoroughly describe the construction process of a species‐specific ML‐based binary classification phenological model that is suitable for phenological predictions in both spring and autumn. Through experiments, we evaluate 18 commonly used ML classification algorithms and the effects of two parameters on the prediction performance of the model. Finally, we compare the performance between the binary classification model and six widely used ecophysiological models for accuracy of spring phenological prediction. Main conclusions The median root mean square error (RMSE) of the binary classification model for the first flowering date (93 observation series) was only 2.99 days, which proves that it is a good method of phenological prediction for temperate trees. This model can effectively overcome the insufficient sample size of ground observations for specific species and provide new insights of phenological predictions for tropical and subtropical trees. The comparison of different ML algorithms showed that the median root mean square errors of the six algorithms were 3.7 days) in prediction of spring phenology. In addition, this model can help us to infer plant physiological mechanisms and drivers of phenological change and provide more accurate predictions of plant phenological responses to climate change.

Climate warming shifts the time interval between flowering and leaf unfolding depending on the warming period - Shuxin Wang; Zhaofei Wu; Yufeng Gong; Shubiao Wang; Wei Zhang; Shanshan Zhang; Hans J. De Boeck; Yongshuo H. Fu (Science China Life Sciences, 2022)

Winter warming offsets one half of the spring warming effects on leaf unfolding - Huanjiong Wang; Junhu Dai; Josep Peñuelas; Quansheng Ge; Yongshuo H. Fu; Chaoyang Wu (Global Change Biology, 2022)
Winter temperature‐related chilling and spring temperature‐related forcing are two major environmental cues shaping the leaf‐out date of temperate species. To what degree insufficient chilling caused by winter warming would slow phenological responses to spring warming remains unclear. Using 27,071 time series of leaf‐out dates for 16 tree species in Europe, we constructed a phenological model based on the linear or exponential function between the chilling accumulation (CA) and forcing requirements (FR) of leaf‐out. We further used the phenological model to quantify the relative contributions of chilling and forcing on past and future spring phenological change. The results showed that the delaying effect of decreased chilling on the leaf‐out date was prevalent in natural conditions, as more than 99% of time series exhibited a negative relationship between CA and FR. The reduction in chilling linked to winter warming from 1951 to 2014 could offset about one half of the spring phenological advance caused by the increase in forcing. In future warming scenarios, if the same model is used and a linear, stable correlation between CA and FR is assumed, declining chilling will continuously offset the advance of leaf‐out to a similar degree. Our study stresses the importance of assessing the antagonistic effects of winter and spring warming on leaf‐out phenology.

Soil moisture regulates warming responses of autumn photosynthetic transition dates in subtropical forests - Yongshuo H. Fu; Xinxi Li; Shouzhi Chen; Zhaofei Wu; Jianrong Su; Xing Li; Shuaifeng Li; Jing Zhang; Jing Tang; Jingfeng Xiao (Global Change Biology, 2022)
Autumn phenology plays a key role in regulating the terrestrial carbon and water balance and their feedbacks to the climate. However, the mechanisms underlying autumn phenology are still poorly understood, especially in subtropical forests. In this study, we extracted the autumn photosynthetic transition dates (APTD) in subtropical China over the period 2003–2017 based on a global, fine‐resolution solar‐induced chlorophyll fluorescence (SIF) dataset (GOSIF) using four fitting methods, and then explored the temporal–spatial variations of APTD and its underlying mechanisms using partial correlation analysis and machine learning methods. We further predicted the APTD shifts under future climate warming conditions by applying process‐based and machine learning‐based models. We found that the APTD was significantly delayed, with an average rate of 7.7 days per decade, in subtropical China during 2003–2017. Both partial correlation analysis and machine learning methods revealed that soil moisture was the primary driver responsible for the APTD changes in southern subtropical monsoon evergreen forest (SEF) and middle subtropical evergreen forest (MEF), whereas solar radiation controlled the APTD variations in the northern evergreen‐broadleaf deciduous mixed forest (NMF). Combining the effects of temperature, soil moisture and radiation, we found a significantly delayed trend in APTD during the 2030–2100 period, but the trend amplitude (0.8 days per decade) was much weaker than that over 2003–2017. In addition, we found that machine learning methods outperformed process‐based models in projecting APTD. Our findings generate from different methods highlight that soil moisture is one of the key players in determining autumn photosynthetic phenological processes in subtropical forests. To comprehensively understand autumn phenological processes, in‐situ manipulative experiments are urgently needed to quantify the contributions of different environmental and physiological factors in regulating plants' response to ongoing climate change.

Field engineering application of agricultural farmland surface runoff pollution treatment by combined bioreactor and constructed wetlands - H. Luo; X. Li; Y. Chen; X. Liu; K. Zhang; X. Fu; B. Jiang; R. Xue; J. Yang; M. Li; X. Li; W. Chen; et al. (International Journal of Environmental Science and Technology, 2022)

Extraction and analysis of an organophosphate salt nucleating agent from irradiated polypropylene resin - Mary Dawn Celiz; Kim M. Morehouse; Clark D. Ridge; Fu Chen; Lowri S. deJager; Timothy H. Begley (Food Additives & Contaminants: Part A, 2022)

Effects of environmental factors on release amount of heavy metal and structure of microbial community in sediments - T. Wen; H. Zhong; G. Fu; Y. Zhong (International Journal of Environmental Science and Technology, 2022)

Higher temperature sensitivity of flowering than leaf‐out alters the time between phenophases across temperate tree species - Xiaojun Geng; Yongshuo H. Fu; Shilong Piao; Fanghua Hao; Hans J. De Boeck; Xuan Zhang; Shouzhi Chen; Yahui Guo; Janet S. Prevéy; Yann Vitasse; Josep Peñuelas; Ivan A. Janssens; et al. (Global Ecology and Biogeography, 2022)
Aim The aims of this study were to evaluate the changes in the length of the time period between leaf‐out and flowering across temperate tree species, and associate these changes with potential physiological and environmental drivers to enhance mechanistic insight into these phenomena. Location Central Europe. Time period 1980–2016. Major taxa studied Six temperate woody species. Methods Statistical analyses were carried out based on long‐term ground observations of both spring leaf‐out and flowering across temperate tree species during 1980–2016, a period characterized by rapid warming. Results The temperature sensitivity of flowering (−5.4 ± 0.04 days/℃, mean ± SE ) was higher than that of leaf‐out (−4.6 ± 0.04 days/℃) across all species, regardless of whether leaf‐out occurred before or after flowering. This study postulates a hypothesis attributing the different temperature sensitivities to different thermal sensitivities, thermal requirements, and photoperiodic controls. Main conclusions The larger temperature sensitivity of flowering than leaf‐out resulted in an extended time period between flowering and leaf‐out in species that bloom before leafing out, but a shorter time period between these phenophases in species with the opposite strategy. We would like to emphasize the importance of changes in time period between different phenophases, and we recommend conducting experimental research to reveal the underlying mechanisms of plant phenology response to climate change, and to explore its potential ecological implications.

Documenting pollinators, floral hosts, and plant–pollinator interactions in U.S. P acific N orthwest agroecosystems - Elias H. Bloom; Elisabeth C. Oeller; Rachel L. Olsson; Matthew R. Brousil; Robert N. Schaeffer; Saumik Basu; Zhen Fu; David W. Crowder (Ecology, 2022)
The abundance and diversity of pollinator populations are in global decline. Managed pollinator species, like honey bees, and wild species are key ecosystem service providers in both natural and managed agroecosystems. However, relatively few studies have exhaustively characterized pollinator populations in diverse agroecosystems over multiple years, while also thoroughly documenting plant–pollinator interactions. Yet, such studies are needed to fulfill the national pollinator protection plans that have been released by the United States and other nations. Our research is among the first studies to respond to these directives by systematically documenting bee and plant biodiversity, bee–plant interactions, and bee‐mediated pollen movement in farming systems of the Pacific Northwest, USA. Our data provides insight into the processes mediating pollinator and plant community assembly, persistence, and resilience across landscapes with variable crop and landscape diversity and agroecosystem management practices. These data will also contribute to the development of a United States pollinator database, supporting the United States' plan to promote pollinators. With few publicly available data sets that systematically take account of agroecosystem practices, plant populations, and pollinators, our research will provide future users the means to conduct synesthetic studies of pollinators and ecosystem function in a period of rapid and global pollinator declines. There are no copyright or proprietary restrictions for research or teaching purposes. Usage of the data set must be cited.

PL57 garnet as a new natural reference material for in situ U–Pb isotope analysis and its perspective for geological applications - Dengfeng Li; Yu Fu; Pete Hollings; Roger H. Mitchell; Shannon Zurevinski; Sandra Kamo; Rongqing Zhang; Yu Zhang; Qiaofen Liu; Jianlin Liao; Yongjia Liang; Xiaoming Sun (Contributions to Mineralogy and Petrology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Atmospheric brightening counteracts warming‐induced delays in autumn phenology of temperate trees in Europe - Zhaofei Wu; Shouzhi Chen; Hans J. De Boeck; Nils Christian Stenseth; Jing Tang; Yann Vitasse; Shuxin Wang; Constantin Zohner; Yongshuo H. Fu (Global Ecology and Biogeography, 2021)
Aim Ongoing climate warming has been widely reported to delay autumn phenology, which in turn impacts carbon, water, energy and nutrient balances at regional and global scales. However, the underlying mechanisms of autumn phenology responses to climate change have not been fully elucidated. The aims of this study were to determine whether brightening that was defined as the increase of surface solar radiation and warming during recent decades affect autumn phenology in opposite directions and explore the underlying mechanisms. Location Central Europe. Time period 1950–2016. Major taxa studied Four dominant European tree species in central Europe: Aesculus hippocastanum , Betula pendula , Fagus sylvatica and Quercus robur . Methods We investigated the temporal trends of leaf senescence, preseason temperature and radiation by separating the period of 1950–2016 into two sub‐periods (1950–1982 and 1983–2016) and determined the relationship between temperature, radiation and leaf senescence using partial correlation analysis. Results We found a significant warming and brightening trend after the 1980s in central Europe, yet this led to only slight delays in leaf senescence that cannot be explained by the well‐known positive correlation between leaf senescence and autumn warming. Interestingly, we found opposite effects between warming (partial correlation coefficient, r = .37) and brightening ( r = −.23) on leaf senescence. In addition, the temperature sensitivity of leaf senescence decreased with increasing radiation (−5.08 days/℃/10 8 J/m 2 ). Main conclusions The results suggested that brightening accelerated the leaf senescence dates, counteracting the warming‐induced delays in leaf senescence, which may be attributed to photooxidative stress and/or sink limitation. This emphasizes the need to consider radiation to improve the performance of autumn phenology models.

The Santa Lúcia Cu-Au deposit, Carajás Mineral Province, Brazil: a Neoarchean (2.68 Ga) member of the granite-related copper-gold systems of Carajás - Raphael B. Hunger; Gustavo H. C. de Melo; Roberto P. Xavier; Carolina P. N. Moreto; Cristina Talavera; Zhi-Kun Su; Xin-Fu Zhao (Mineralium Deposita, 2021)

Genetic Depletion of Amylin/Calcitonin Receptors Improves Memory and Learning in Transgenic Alzheimer’s Disease Mouse Models - Aarti Patel; Ryoichi Kimura; Wen Fu; Rania Soudy; David MacTavish; David Westaway; Jing Yang; Rachel A. Davey; Jeffrey D. Zajac; Jack H. Jhamandas (Molecular Neurobiology, 2021)
Based upon its interactions with amyloid β peptide (Aβ), the amylin receptor, a class B G protein-coupled receptor (GPCR), is a potential modulator of Alzheimer’s disease (AD) pathogenesis. However, past pharmacological approaches have failed to resolve whether activation or blockade of this receptor would have greater therapeutic benefit. To address this issue, we generated compound mice expressing a human amyloid precursor protein gene with familial AD mutations in combination with deficiency of amylin receptors produced by hemizygosity for the critical calcitonin receptor subunit of this heterodimeric GPCR. These compound transgenic AD mice demonstrated attenuated responses to human amylin- and Aβ-induced depression of hippocampal long-term potentiation (LTP) in keeping with the genetic depletion of amylin receptors. Both the LTP responses and spatial memory (as measured with Morris water maze) in these mice were improved compared to AD mouse controls and, importantly, a reduction in both the amyloid plaque burden and markers of neuroinflammation was observed. Our data support the notion of further development of antagonists of the amylin receptor as AD-modifying therapies.

Characteristics and formation mechanisms of Mesozoic compressional structures in the Huanghua Depression, Bohai Bay Basin, China - W. Li; F. Zhang; Y. Zhang; L. Fu; H. Li (Australian Journal of Earth Sciences, 2021)

Decreasing control of precipitation on grassland spring phenology in temperate China - Yongshuo H. Fu; Xuancheng Zhou; Xinxi Li; Yaru Zhang; Xiaojun Geng; Fanghua Hao; Xuan Zhang; Heikki Hanninen; Yahui Guo; Hans J. De Boeck (Global Ecology and Biogeography, 2021)
Aim Vegetation phenology is highly sensitive to climate change. The timing of spring phenology in temperate grasslands is regulated primarily by temperature and precipitation. The aim of this study was to determine whether the primary factor regulating vegetation phenology has changed under ongoing climate change and the underlying mechanisms. Location Temperate semi‐dry grasslands in China. Time period 1982–2015. Major taxa studied Temperate grassland. Methods We extracted start of season (SOS) dates using five standard methods from satellite‐derived normalized difference vegetation index (NDVI) data and determined the primary factor regulating spring phenology using partial correlation analysis. Results The SOS date did not change significantly during the entire 1982–2015 study period in these semi‐dry grasslands, but interannual variability increased significantly from the first subperiod [1982–1998, 8.8 ± 1.1 days (mean ± SE )] to the second subperiod (1999–2015, 10.3 ± 1.1 days). Interestingly, we found that the primary factor regulating SOS shifted from precipitation during 1982–1998 to temperature during 1999–2015. Specifically, we found that during the first period, the SOS in 67.5% of the study area was determined by precipitation (mean partial correlation coefficient, r = 0.58 ± 0.16), but during the second period the main regulating factor in 75.0% of the study area was temperature ( r = 0.61 ± 0.14). Main conclusions The change in the primary driver of spring phenology was attributed mainly to significant increases in preseason precipitation. Our study highlights that the response of spring phenology to climatic factors might change under ongoing climate change. This shift should be addressed in phenology models to simulate grassland phenology better, in addition to its impact on carbon and water cycles in future climate conditions.

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Climate warming increases spring phenological differences among temperate trees - Xiaojun Geng; Yongshuo H. Fu; Fanghua Hao; Xuancheng Zhou; Xuan Zhang; Guodong Yin; Yann Vitasse; Shilong Piao; Kechang Niu; Hans J. De Boeck; Annette Menzel; Josep Peñuelas (Global Change Biology, 2020)
Climate warming has substantially advanced spring leaf flushing, but winter chilling and photoperiod co‐determine the leaf flushing process in ways that vary among species. As a result, the interspecific differences in spring phenology (IDSP) are expected to change with climate warming, which may, in turn, induce negative or positive ecological consequences. However, the temporal change of IDSP at large spatiotemporal scales remains unclear. In this study, we analyzed long‐term in‐situ observations (1951–2016) of six, coexisting temperate tree species from 305 sites across Central Europe and found that phenological ranking did not change when comparing the rapidly warming period 1984–2016 to the marginally warming period 1951–1983. However, the advance of leaf flushing was significantly larger in early‐flushing species EFS (6.7 ± 0.3 days) than in late‐flushing species LFS (5.9 ± 0.2 days) between the two periods, indicating extended IDSP. This IDSP extension could not be explained by differences in temperature sensitivity between EFS and LFS; however, climatic warming‐induced heat accumulation effects on leaf flushing, which were linked to a greater heat requirement and higher photoperiod sensitivity in LFS, drove the shifts in IDSP. Continued climate warming is expected to further extend IDSP across temperate trees, with associated implications for ecosystem function.

Free fatty acid receptor 4 activation protects against choroidal neovascularization in mice - Yohei Tomita; Bertan Cakir; Chi-Hsiu Liu; Zhongjie Fu; Shuo Huang; Steve S. Cho; William R. Britton; Ye Sun; Mark Puder; Ann Hellström; Saswata Talukdar; Lois E. H. Smith (Angiogenesis, 2020)

Modeling leaf senescence of deciduous tree species in Europe - Qiang Liu; Shilong Piao; Matteo Campioli; Mengdi Gao; Yongshuo H. Fu; Kai Wang; Yue He; Xiangyi Li; Ivan A. Janssens (Global Change Biology, 2020)
Autumnal leaf senescence signals the end of photosynthetic activities in temperate deciduous trees and consequently exerts a strong control on various ecological processes. Predicting leaf senescence dates (LSD) with high accuracy is thus a prerequisite for better understanding the climate–ecosystem interactions. However, modeling LSD at large spatial and temporal scales is challenging. In this study, first, we used 19972 site‐year records (848 sites and four deciduous tree species) from the PAN European Phenology network to calibrate and evaluate six leaf senescence models during the period 1980–2013. Second, we extended the spatial analysis by repeating the procedure across Europe using satellite‐derived end of growing season and a forest map. Overall, we found that models that considered photoperiod and temperature interactions outperformed models using simple temperature or photoperiod thresholds for Betula pendula , Fagus sylvatica and Quercus robur . On the contrary, no model displayed reasonable predictions for Aesculus hippocastanum . This inter‐model comparison indicates that, contrary to expectation, photoperiod does not significantly modulate the accumulation of cooling degree days (CDD). On the other hand, considering the carryover effect of leaf unfolding date could promote the models’ predictability. The CDD models generally matched the observed LSD at species level and its interannual variation, but were limited in explaining the inter‐site variations, indicating that other environmental cues need to be considered in future model development. The discrepancies remaining between model simulations and observations highlight the need of manipulation studies to elucidate the mechanisms behind the leaf senescence process and to make current models more realistic.

Specific genes and sequence variation in pathotype 7 of the clubroot pathogen Plasmodiophora brassicae - H. Yang; J. Zheng; Y. D. Fu; Y. H. Zhang; C. L. Yi; C. Jin; Y. Huang; Wenming Wang (European Journal of Plant Pathology, 2020)

The southern Amazon rainy season: The role of deforestation and its interactions with large‐scale mechanisms - Argemiro T. Leite‐Filho; Marcos H. Costa; Rong Fu (International Journal of Climatology, 2020)
Past studies presented evidence that deforestation may affect the precipitation seasonality in southern Amazon. This study uses daily rainfall data from Tropical Rainfall Measurement Mission 3B42 product and a recent yearly 1‐km land use dataset to evaluate the quantitative effects of deforestation on the onset, demise and length of the rainy season in southern Amazon for a period of 15 years (1998–2012). Additionally, we use the Niño4 index, zonal wind data and deforestation data to explain and predict the interannual variability of the onset of the rainy season. During this period, onset has delayed ~0.38 ± 0.05 days per year (5.7 ± 0.75 days in 15 years), demise has advanced 1.34 ± 0.76 days per year (20 ± 11.4 days in 15 years) and the rainy season has shortened by 1.81 ± 0.97 days per year (27 ± 14.5 days in 15 years). Onset, demise and length also present meridional and zonal gradients linked to large‐scale climate mechanisms. After removing the effects related to geographical position and year, we verified a relationship between onset, demise and length and deforestation: Onset delays ~0.4 ± 0.12 day, demise advances ~1.0 ± 0.22 day and length decreases ~0.9 ± 0.34 day per each 10% deforestation increase relative to existing forested area. We also present empirical evidence of the interaction between large‐scale and local‐scale processes, with interannual variation of the onset in the region explained by Niño4 sea surface temperature anomalies, Southern Hemisphere subtropical jet position, deforestation and their interactions ( r 2 = 69%, p

Effects of urease and nitrification inhibitors on soil N, nitrifier abundance and activity in a sandy loam soil - Qingling Fu; Maïder Abadie; Aimeric Blaud; Alison Carswell; Tom H. Misselbrook; Ian M. Clark; Penny R. Hirsch (Biology and Fertility of Soils, 2020)
Inhibitors of urease and ammonia monooxygenase can limit the rate of conversion of urea to ammonia and ammonia to nitrate, respectively, potentially improving N fertilizer use efficiency and reducing gaseous losses. Winter wheat grown on a sandy soil in the UK was treated with urea fertilizer with the urease inhibitor N-(n-butyl) thiophosphoric triamide (NBPT), the nitrification inhibitor dicyandiamide (DCD) or a combination of both. The effects on soil microbial community diversity, the abundance of genes involved in nitrification and crop yields and net N recovery were compared. The only significant effect on N-cycle genes was a transient reduction in bacterial ammonia monooxygenase abundance following DCD application. However, overall crop yields and net N recovery were significantly lower in the urea treatments compared with an equivalent application of ammonium nitrate fertilizer, and significantly less for urea with DCD than the other urea treatments.

Characteristics changes in banana peel coagulant during storage process - Y. Fu; X. J. Meng; N. N. Lu; H. L. Jian; Y. Di (International Journal of Environmental Science and Technology, 2019)

Evaluation of Stripe Rust Resistance in Hungarian Winter Wheat Cultivars in China - D. Huang; H. Zhang; M. Tar; Y. Zhang; F. Ni; J. Ren; D. Fu; L. Purnhauser; J. Wu (Cereal Research Communications, 2019)

Shortened temperature‐relevant period of spring leaf‐out in temperate‐zone trees - Yongshuo H. Fu; Xiaojun Geng; Fanghua Hao; Yann Vitasse; Constantin M. Zohner; Xuan Zhang; Xuancheng Zhou; Guodong Yin; Josep Peñuelas; Shilong Piao; Ivan A. Janssens (Global Change Biology, 2019)
Temperature during a particular period prior to spring leaf‐out, the temperature‐relevant period (TRP), is a strong determinant of the leaf‐out date in temperate‐zone trees. Climatic warming has substantially advanced leaf‐out dates in temperate biomes worldwide, but its effect on the beginning and length of the TRP has not yet been explored, despite its direct relevance for phenology modeling. Using 1,551 species–site combinations of long‐term (1951–2016) in situ observations on six tree species (namely, Aesculus hippocastanum , Alnus glutinosa , Betula pendula , Fagus sylvatica , Fraxinus excelsior , and Quercus robur ) in central Europe, we found that the advancing leaf‐out was accompanied by a shortening of the TRP. On average across all species and sites, the length of the TRP significantly decreased by 23% ( p

Different determinants of radiation use efficiency in cold and temperate forests - Manuela Balzarolo; Nadia Valdameri; Yongshuo H. Fu; Lennert Schepers; Ivan A. Janssens; Matteo Campioli (Global Ecology and Biogeography, 2019)
Aim To verify which vegetation and environmental factors are the most important in determining the spatial and temporal variability of average and maximum values of radiation use efficiency (RUE ann and RUE max , respectively) of cold and temperate forests. Location Forty‐eight cold and temperate forests distributed across the Northern Hemisphere. Major taxa studied Evergreen and deciduous trees. Time period 2000–2011. Methods We analysed the impact of 17 factors as potential determinants of mean RUE (at 8 days interval, annual and interannual level) and RUE max (at annual and interannual level) in cold and temperate forests by using linear regression and random forests models. Results Mean annual RUE (RUE ann , c. 1.1 gC/MJ) and RUE max ( c. 0.8 gC/MJ) did not differ between cold and temperate forests. However, for cold forests, RUE ann was affected by temperature‐related variables, while for temperate forests RUE ann was affected by drought‐related variables. Leaf area index (LAI) was important for both forest types, while N deposition only for cold forests and cloud cover only for temperate forest. RUE max of cold forests was mainly driven by N deposition and LAI, whereas for temperate forests only a weak relationship between RUE max and CO 2 concentration was found. Short‐term variability of RUE was strongly related to the meteorological variables and varied during the season and was stronger in summer than spring or autumn. Interannual variability of RUE ann and RUE max was only weakly related to the interannual variability of the environmental drivers. Main conclusions Cold and temperate forests show different relationships with the environment and vegetation properties. Among the RUE drivers observed, the least anticipated was N deposition. RUE is strongly related to short‐term and seasonal changes in meteorological variables among seasons and among sites. Our results should be considered in the formulation of climate zone‐specific tools for remote sensing and global models.

African Orphan Crops Consortium (AOCC): status of developing genomic resources for African orphan crops - Prasad S. Hendre; Samuel Muthemba; Robert Kariba; Alice Muchugi; Yuan Fu; Yue Chang; Bo Song; Huan Liu; Min Liu; Xuezhu Liao; Sunil Kumar Sahu; Sibo Wang; et al. (Planta, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Daylength helps temperate deciduous trees to leaf‐out at the optimal time - Yongshuo H. Fu; Xuan Zhang; Shilong Piao; Fanghua Hao; Xiaojun Geng; Yann Vitasse; Constantin Zohner; Josep Peñuelas; Ivan A. Janssens (Global Change Biology, 2019)
Global warming has led to substantially earlier spring leaf‐out in temperate‐zone deciduous trees. The interactive effects of temperature and daylength underlying this warming response remain unclear. However, they need to be accurately represented by earth system models to improve projections of the carbon and energy balances of temperate forests and the associated feedbacks to the Earth's climate system. We studied the control of leaf‐out by daylength and temperature using data from six tree species across 2,377 European phenological network ( www.pep725.eu ), each with at least 30 years of observations. We found that, in addition to and independent of the known effect of chilling, daylength correlates negatively with the heat requirement for leaf‐out in all studied species. In warm springs when leaf‐out is early, days are short and the heat requirement is higher than in an average spring, which mitigates the warming‐induced advancement of leaf‐out and protects the tree against precocious leaf‐out and the associated risks of late frosts. In contrast, longer‐than‐average daylength (in cold springs when leaf‐out is late) reduces the heat requirement for leaf‐out, ensuring that trees do not leaf‐out too late and miss out on large amounts of solar energy. These results provide the first large‐scale empirical evidence of a widespread daylength effect on the temperature sensitivity of leaf‐out phenology in temperate deciduous trees.

Short photoperiod reduces the temperature sensitivity of leaf‐out in saplings of Fagus sylvatica but not in horse chestnut - Yongshuo H. Fu; Shilong Piao; Xuancheng Zhou; Xiaojun Geng; Fanghua Hao; Yann Vitasse; Ivan A. Janssens (Global Change Biology, 2019)
Leaf phenology is one of the most reliable bioindicators of ongoing global warming in temperate and boreal zones because it is highly sensitive to temperature variation. A large number of studies have reported advanced spring leaf‐out due to global warming, yet the temperature sensitivity of leaf‐out has significantly decreased in temperate deciduous tree species over the past three decades. One of the possible mechanisms is that photoperiod is limiting further advance to protect the leaves against potential damaging frosts. However, the “photoperiod limitation” hypothesis remains poorly investigated and experimentally tested. Here, we conducted a photoperiod‐ and temperature‐manipulation experiment in climate chambers on two common deciduous species in Europe: Fagus sylvatica (European beech, a typically late flushing species) and Aesculus hippocastanum (horse chestnut, a typically early flushing species). In agreement with previous studies, we found that the warming significantly advanced the leaf‐out dates by 4.3 and 3.7 days/°C for beech and horse chestnut saplings, respectively. However, shorter photoperiod significantly reduced the temperature sensitivity of beech only (3.0 days/°C) by substantially increasing the heat requirement to avoid leafing‐out too early. Interestingly, the photoperiod limitation only occurs below a certain daylength (photoperiod threshold) when the warming increased above 4°C for beech trees. In contrast, for chestnut, no photoperiod threshold was found even when the ambient air temperature was warmed by 5°C. Given the species‐specific photoperiod effect on leaf phenology, the sequence of the leaf‐out timing among forest tree species may change under future climate warming conditions. Nonphotoperiodic species may benefit from warmer springs by starting the growing season earlier than photoperiodic sensitive species, modifying forest ecosystem structure and functions, but this photoperiod limitation needs to be further investigated experimentally in numerous specie s .

Sequence stratigraphy and Quaternary depositional systems in the Sanhu area of the Qaidam Basin, northwest China - Z. Liu; S. Fu; H. C. Jia; J. X. Tian; Y. H. Chen; C. Y. Dong (Australian Journal of Earth Sciences, 2019)

Genome-wide identification and functional analysis of the splicing component SYF2/NTC31/p29 across different plant species - Yuan Tian; Mo-Xian Chen; Jing-Fang Yang; H. H. K. Achala; Bei Gao; Ge-Fei Hao; Guang-Fu Yang; Zhi-Yong Dian; Qi-Juan Hu; Di Zhang; Jianhua Zhang; Ying-Gao Liu (Planta, 2019)

Generation of multi-site stochastic daily rainfall with four weather generators: a case study of Gloucester catchment in Australia - Guobin Fu; Francis H. S. Chiew; Xiaogang Shi (Theoretical and Applied Climatology, 2018)

Quantitative discrimination of normal fault segment growth and its geological significance: example from the Tanan Depression, Tamtsag Basin, Mongolia - H. X. Wang; X. F. Fu; S. R. Liu; R. Chu; B. Liu; P. P. Shi (Australian Journal of Earth Sciences, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

A cardioid oscillator with asymmetric time ratio for establishing CPG models - Q. Fu; D. H. Wang; L. Xu; G. Yuan (Biological Cybernetics, 2018)

Larger temperature response of autumn leaf senescence than spring leaf‐out phenology - Yongshuo H. Fu; Shilong Piao; Nicolas Delpierre; Fanghua Hao; Heikki Hänninen; Yongjie Liu; Wenchao Sun; Ivan A. Janssens; Matteo Campioli (Global Change Biology, 2018)
Climate warming is substantially shifting the leaf phenological events of plants, and thereby impacting on their individual fitness and also on the structure and functioning of ecosystems. Previous studies have largely focused on the climate impact on spring phenology, and to date the processes underlying leaf senescence and their associated environmental drivers remain poorly understood. In this study, experiments with temperature gradients imposed during the summer and autumn were conducted on saplings of European beech to explore the temperature responses of leaf senescence. An additional warming experiment during winter enabled us to assess the differences in temperature responses of spring leaf‐out and autumn leaf senescence. We found that warming significantly delayed the dates of leaf senescence both during summer and autumn warming, with similar temperature sensitivities (6–8 days delay per °C warming), suggesting that, in the absence of water and nutrient limitation, temperature may be a dominant factor controlling the leaf senescence in European beech. Interestingly, we found a significantly larger temperature response of autumn leaf senescence than of spring leaf‐out. This suggests a possible larger contribution of delays in autumn senescence, than of the advancement in spring leaf‐out, to extending the growing season under future warmer conditions.

An Efficient and Reliable Assay for Investigating the Effects of Hypoxia/Anoxia on Drosophila - Yiling Xia; Wangchao Xu; Shiquan Meng; Nastasia K. H. Lim; Wenan Wang; Fu-De Huang (Neuroscience Bulletin, 2018)

Simulating the onset of spring vegetation growth across the Northern Hemisphere - Qiang Liu; Yongshuo H. Fu; Yongwen Liu; Ivan A. Janssens; Shilong Piao (Global Change Biology, 2018)
Changes in the spring onset of vegetation growth in response to climate change can profoundly impact climate–biosphere interactions. Thus, robust simulation of spring onset is essential to accurately predict ecosystem responses and feedback to ongoing climate change. To date, the ability of vegetation phenology models to reproduce spatiotemporal patterns of spring onset at larger scales has not been thoroughly investigated. In this study, we took advantage of phenology observations via remote sensing to calibrate and evaluated six models, including both one‐phase (considering only forcing temperatures) and two‐phase (involving forcing, chilling, and photoperiod) models across the Northern Hemisphere between 1982 and 2012. Overall, we found that the model that integrated the photoperiod effect performed best at capturing spatiotemporal patterns of spring phenology in boreal and temperate forests. By contrast, all of the models performed poorly in simulating the onset of growth in grasslands. These results suggest that the photoperiod plays a role in controlling the onset of growth in most Northern Hemisphere forests, whereas other environmental factors (e.g., precipitation) should be considered when simulating the onset of growth in grasslands. We also found that the one‐phase model performed as well as the two‐phase models in boreal forests, which implies that the chilling requirement is probably fulfilled across most of the boreal zone. Conversely, two‐phase models performed better in temperate forests than the one‐phase model, suggesting that photoperiod and chilling play important roles in these temperate forests. Our results highlight the significance of including chilling and photoperiod effects in models of the spring onset of forest growth at large scales, and indicate that the consideration of additional drivers may be required for grasslands.

Sealed tube promoted coupling of camptothecin and norcantharidin acid ester and their preliminary biological activity evaluation in vitro - Xian H. Wang; Fu H. Yang; Chang K. Zhao; Lei Gao; Chan Li (Medicinal Chemistry Research, 2018)

Effects of rate and application method on the efficacy of metam sodium to reduce clubroot (Plasmodiophora brassicae) of canola - S. F. Hwang; H. U. Ahmed; S. E. Strelkov; Q. Zhou; B. D. Gossen; G. Peng; G. D. Turnbull; H. Fu (European Journal of Plant Pathology, 2018)

High genetic diversity and differentiation in three red tilapia stocks revealed by microsatellite DNA marker analysis - W.B. Zhu; H. Yang; X.H. Yuan; Z.J. Dong; J.J. Fu; L.M. Wang; S.Y. Su; N. Liu; F.B. Song; X.T. Chen (Aquaculture International, 2017)

Asymmetric effects of cooler and warmer winters on beech phenology last beyond spring - Constant Signarbieux; Ester Toledano; Paula Sanginés de Carcer; Yongshuo H. Fu; Rodolphe Schlaepfer; Alexandre Buttler; Yann Vitasse (Global Change Biology, 2017)
In temperate trees, the timings of plant growth onset and cessation affect biogeochemical cycles, water, and energy balance. Currently, phenological studies largely focus on specific phenophases and on their responses to warming. How differently spring phenology responds to the warming and cooling, and affects the subsequent phases, has not been yet investigated in trees. Here, we exposed saplings of Fagus sylvatica L. to warmer and cooler climate during the winter 2013–2014 by conducting a reciprocal transplant experiment between two elevations (1,340 vs. 371 m a.s.l., ca. 6°C difference) in the Swiss Jura mountains. To test the legacy effects of earlier or later budburst on the budset timing, saplings were moved back to their original elevation shortly after the occurrence of budburst in spring 2014. One degree decrease in air temperature in winter/spring resulted in a delay of 10.9 days in budburst dates, whereas one degree of warming advanced the date by 8.8 days. Interestingly, we also found an asymmetric effect of the warmer winter vs. cooler winter on the budset timing in late summer. Budset of saplings that experienced a cooler winter was delayed by 31 days compared to the control, whereas it was delayed by only 10 days in saplings that experienced a warmer winter. Budburst timing in 2015 was not significantly impacted by the artificial advance or delay of the budburst timing in 2014, indicating that the legacy effects of the different phenophases might be reset during each winter. Adapting phenological models to the whole annual phenological cycle, and considering the different response to cooling and warming, would improve predictions of tree phenology under future climate warming conditions.

Computational Analysis on Down-Regulated Images of Macrophage Scavenger Receptor - Byeongtaek Oh; Yugyung Lee; Mingui Fu; Chi H. Lee (Pharmaceutical Research, 2017)

Reservoir characteristics and methane adsorption capacity of the Upper Triassic continental shale in Western Sichuan Depression, China - Y. C. Liu; D. X. Chen; N. S. Qiu; Y. Wang; J. Fu; Y. Huyan; J. K. Jia; H. Wu (Australian Journal of Earth Sciences, 2017)

Elements in Fine Particulate Matter (PM $$_{2.5}$$ 2.5 ) from Indoor Air During Household Stoves Coal Combustion at Xuanwei, China - K. H. Lui; C. S. Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Jinwen Li; Jun-Ji Cao; S. C. Lee; K. F. Ho (Aerosol Science and Engineering, 2017)

Molecular taxonomy and morphological characterization reveal new species and new host records of Torula species (Torulaceae, Pleosporales) - Jun-Fu Li; Rungtiwa Phookamsak; Rajesh Jeewon; Darbhe J. Bhat; Ausana Mapook; Erio Camporesi; Qiu-Ju Shang; Ekachai Chukeatirote; Ali H. Bahkali; Kevin D. Hyde (Mycological Progress, 2017)

A GCM investigation of impact of aerosols on the precipitation in Amazon during the dry to wet transition - Yu Gu; K. N. Liou; J. H. Jiang; R. Fu; Sarah Lu; Y. Xue (Climate Dynamics, 2017)

Rotor Tracking Using Phase of Electrograms Recorded During Atrial Fibrillation - Caroline H. Roney; Chris D. Cantwell; Norman A. Qureshi; Rasheda A. Chowdhury; Emmanuel Dupont; Phang Boon Lim; Edward J. Vigmond; Jennifer H. Tweedy; Fu Siong Ng; Nicholas S. Peters (Annals of Biomedical Engineering, 2017)

A comprehensive approach from the raw and normalized anomalies to the analysis and prediction of the Beijing extreme rainfall on July 21, 2012 - Ning Jiang; Weihong Qian; Jun Du; Richard H. Grumm; Jiaolan Fu (Natural Hazards, 2016)

Long-term linear trends mask phenological shifts - Yongshuo H Fu; Shilong Piao; Philippe Ciais; Mengtian Huang; Annette Menzel; Marc Peaucelle; Shushi Peng; Yang Song; Yann Vitasse; Zhenzhong Zeng; Hongfang Zhao; Guiyun Zhou; et al. (International Journal of Biometeorology, 2016)

Delayed autumn phenology in the Northern Hemisphere is related to change in both climate and spring phenology - Qiang Liu; Yongshuo H. Fu; Zaichun Zhu; Yongwen Liu; Zhuo Liu; Mengtian Huang; Ivan A. Janssens; Shilong Piao (Global Change Biology, 2016)
The timing of the end of the vegetation growing season ( EOS ) plays a key role in terrestrial ecosystem carbon and nutrient cycles. Autumn phenology is, however, still poorly understood, and previous studies generally focused on few species or were very limited in scale. In this study, we applied four methods to extract EOS dates from NDVI records between 1982 and 2011 for the Northern Hemisphere, and determined the temporal correlations between EOS and environmental factors (i.e., temperature, precipitation and insolation), as well as the correlation between spring and autumn phenology, using partial correlation analyses. Overall, we observed a trend toward later EOS in ~70% of the pixels in Northern Hemisphere, with a mean rate of 0.18 ± 0.38 days yr −1 . Warming preseason temperature was positively associated with the rate of EOS in most of our study area, except for arid/semi‐arid regions, where the precipitation sum played a dominant positive role. Interestingly, increased preseason insolation sum might also lead to a later date of EOS . In addition to the climatic effects on EOS , we found an influence of spring vegetation green‐up dates on EOS , albeit biome dependent. Our study, therefore, suggests that both environmental factors and spring phenology should be included in the modeling of EOS to improve the predictions of autumn phenology as well as our understanding of the global carbon and nutrient balances.

Strong impacts of daily minimum temperature on the green‐up date and summer greenness of the Tibetan Plateau - Miaogen Shen; Shilong Piao; Xiaoqiu Chen; Shuai An; Yongshuo H. Fu; Shiping Wang; Nan Cong; Ivan A. Janssens (Global Change Biology, 2016)
Understanding vegetation responses to climate change on the Tibetan Plateau ( TP ) helps in elucidating the land–atmosphere energy exchange, which affects air mass movement over and around the TP . Although the TP is one of the world's most sensitive regions in terms of climatic warming, little is known about how the vegetation responds. Here, we focus on how spring phenology and summertime greenness respond to the asymmetric warming, that is, stronger warming during nighttime than during daytime. Using both in situ and satellite observations, we found that vegetation green‐up date showed a stronger negative partial correlation with daily minimum temperature ( T min ) than with maximum temperature ( T max ) before the growing season (‘preseason’ henceforth). Summer vegetation greenness was strongly positively correlated with summer T min , but negatively with T max . A 1‐K increase in preseason T min advanced green‐up date by 4 days ( P P 0.01). In contrast, increases in preseason T max did not advance green‐up date ( P > 0.10) and higher summer T max even reduced greenness by 2.6% K −1 ( P 0.05). The stimulating effects of increasing T min were likely caused by reduced low temperature constraints, and the apparent negative effects of higher T max on greenness were probably due to the accompanying decline in water availability. The dominant enhancing effect of nighttime warming indicates that climatic warming will probably have stronger impact on TP ecosystems than on apparently similar Arctic ecosystems where vegetation is controlled mainly by T max . Our results are crucial for future improvements of dynamic vegetation models embedded in the Earth System Models which are being used to describe the behavior of the Asian monsoon. The results are significant because the state of the vegetation on the TP plays an important role in steering the monsoon.

Public health implications of social media use during natural disasters, environmental disasters, and other environmental concerns - Kathryn C. Finch; Kassandra R. Snook; Carmen H. Duke; King-Wa Fu; Zion Tsz Ho Tse; Atin Adhikari; Isaac Chun-Hai Fung (Natural Hazards, 2016)

Effects of Dietary Selenium Against Lead Toxicity on mRNA Levels of 25 Selenoprotein Genes in the Cartilage Tissue of Broiler Chicken - H Gao; C. P. Liu; S. Q. Song; J. Fu (Biological Trace Element Research, 2016)

Histamine induces the production of matrix metalloproteinase-9 in human astrocytic cultures via H1-receptor subtype - Aarti Patel; Vishnu Vasanthan; Wen Fu; Richard P. Fahlman; David MacTavish; Jack H. Jhamandas (Brain Structure and Function, 2016)

Colored Sticky Traps to Selectively Survey Thrips in Cowpea Ecosystem - L D Tang; H Y Zhao; B L Fu; Y Han; K Liu; J H Wu (Neotropical Entomology, 2016)

Development of roughness updating based on artificial neural network in a river hydraulic model for flash flood forecasting - J C Fu; M H Hsu; Y Duann (Journal of Earth System Science, 2016)

Temperature, precipitation, and insolation effects on autumn vegetation phenology in temperate China - Qiang Liu; Yongshuo H. Fu; Zhenzhong Zeng; Mengtian Huang; Xiran Li; Shilong Piao (Global Change Biology, 2016)
Autumn phenology plays a critical role in regulating climate–biosphere interactions. However, the climatic drivers of autumn phenology remain unclear. In this study, we applied four methods to estimate the date of the end of the growing season ( EOS ) across China's temperate biomes based on a 30‐year normalized difference vegetation index ( NDVI ) dataset from Global Inventory Modeling and Mapping Studies ( GIMMS ). We investigated the relationships of EOS with temperature, precipitation sum, and insolation sum over the preseason periods by computing temporal partial correlation coefficients. The results showed that the EOS date was delayed in temperate China by an average rate at 0.12 ± 0.01 days per year over the time period of 1982–2011. EOS of dry grassland in Inner Mongolia was advanced. Temporal trends of EOS determined across the four methods were similar in sign, but different in magnitude. Consistent with previous studies, we observed positive correlations between temperature and EOS . Interestingly, the sum of precipitation and insolation during the preseason was also associated with EOS , but their effects were biome dependent. For the forest biomes, except for evergreen needle‐leaf forests, the EOS dates were positively associated with insolation sum over the preseason, whereas for dry grassland, the precipitation over the preseason was more dominant. Our results confirmed the importance of temperature on phenological processes in autumn, and further suggested that both precipitation and insolation should be considered to improve the performance of autumn phenology models.

Meta-analyses of structural regional cerebral effects in type 1 and type 2 diabetes - Calum D. Moulton; Sergi G. Costafreda; Paul Horton; Khalida Ismail; Cynthia H. Y. Fu (Brain Imaging and Behavior, 2015)

Increased heat requirement for leaf flushing in temperate woody species over 1980–2012: effects of chilling, precipitation and insolation - Yongshuo H. Fu; Shilong Piao; Yann Vitasse; Hongfang Zhao; Hans J. De Boeck; Qiang Liu; Hui Yang; Ulrich Weber; Heikki Hänninen; Ivan A. Janssens (Global Change Biology, 2015)
Recent studies have revealed large unexplained variation in heat requirement‐based phenology models, resulting in large uncertainty when predicting ecosystem carbon and water balance responses to climate variability. Improving our understanding of the heat requirement for spring phenology is thus urgently needed. In this study, we estimated the species‐specific heat requirement for leaf flushing of 13 temperate woody species using long‐term phenological observations from Europe and North America. The species were defined as early and late flushing species according to the mean date of leaf flushing across all sites. Partial correlation analyses were applied to determine the temporal correlations between heat requirement and chilling accumulation, precipitation and insolation sum during dormancy. We found that the heat requirement for leaf flushing increased by almost 50% over the study period 1980–2012, with an average of 30 heat units per decade. This temporal increase in heat requirement was observed in all species, but was much larger for late than for early flushing species. Consistent with previous studies, we found that the heat requirement negatively correlates with chilling accumulation. Interestingly, after removing the variation induced by chilling accumulation, a predominantly positive partial correlation exists between heat requirement and precipitation sum, and a predominantly negative correlation between heat requirement and insolation sum. This suggests that besides the well‐known effect of chilling, the heat requirement for leaf flushing is also influenced by precipitation and insolation sum during dormancy. However, we hypothesize that the observed precipitation and insolation effects might be artefacts attributable to the inappropriate use of air temperature in the heat requirement quantification. Rather than air temperature, meristem temperature is probably the prominent driver of the leaf flushing process, but these data are not available. Further experimental research is thus needed to verify whether insolation and precipitation sums directly affect the heat requirement for leaf flushing.

Generation of outbred Ace2 knockout mice by RNA transfection of TALENs displaying colitis reminiscent pathophysiology and inflammation - Chuxin Liu; Liping Xiao; Feida Li; Huanhuan Zhang; Qin Li; Huan Liu; Shujin Fu; Chao Li; Xingju Zhang; Jun Wang; Nicklas H. Staunstrup; Yong Li; et al. (Transgenic Research, 2015)

Effect of Biochar in Cadmium Availability and Soil Biological Activity in an Anthrosol Following Acid Rain Deposition and Aging - H. Lu; Z. Li; S. Fu; A. Méndez; G. Gascó; J. Paz-Ferreiro (Water, Air, & Soil Pollution, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Effect of the invasive bivalve Mytilopsis sallei on the macrofaunal fouling community and the environment of Yundang Lagoon, Xiamen, China - L.-Z. Cai; J.-S. Hwang; H.-U. Dahms; S.-J. Fu; Y. Zhuo; T. Guo (Hydrobiologia, 2014)

Quantitative trait analysis of flowering time in spring rapeseed (B. napus L.) - Y. X. Luo; C. Y. Luo; D. Z. Du; Z. Fu; Y. M. Yao; C. C. Xu; H. S. Zhang (Euphytica, 2014)

Role of astrocytic glycolytic metabolism in Alzheimer’s disease pathogenesis - Wen Fu; Jack H. Jhamandas (Biogerontology, 2014)

Unexpected role of winter precipitation in determining heat requirement for spring vegetation green‐up at northern middle and high latitudes - Yongshuo H Fu; Shilong Piao; Hongfang Zhao; Su‐Jong Jeong; Xuhui Wang; Yann Vitasse; Philippe Ciais; Ivan A Janssens (Global Change Biology, 2014)
Heat requirement, expressed in growing degree days ( GDD ), is a widely used method to assess and predict the effect of temperature on plant development. Until recently, the analysis of spatial patterns of GDD requirement for spring vegetation green‐up onset was limited to local and regional scales, mainly because of the sparse and aggregated spatial availability of ground phenology data. Taking advantage of the large temporal and spatial scales of remote sensing‐based green‐up onset data, we studied the spatial patterns of GDD requirement for vegetation green‐up at northern middle and high latitudes. We further explored the correlations between GDD requirement for vegetation green‐up and previous winter season chilling temperatures and precipitation, using spatial partial correlations. We showed that GDD requirement for vegetation green‐up onset declines towards the north at a mean rate of 18.8 °C‐days per degree latitude between 35°N and 70°N, and vary significantly among different vegetation types. Our results confirmed that the GDD requirement for vegetation green‐up is negatively correlated with previous winter chilling, which was defined as the number of chilling days from the day when the land surface froze in the previous autumn to the day of green‐up onset. This negative correlation is a well‐known phenomenon from local studies. Interestingly, irrespective of the vegetation type, we also found a positive correlation between the GDD requirement and previous winter season precipitation, which was defined as the sum of the precipitation of the month when green‐up onset occur and the precipitation that occurred during the previous 2 months. Our study suggests that GDD requirement, chilling and precipitation may have complex interactions in their effects on spring vegetation green‐up phenology. These findings have important implications for improving phenology models and could therefore advance our understanding of the interplay between spring phenology and carbon fluxes.

Recent spring phenology shifts in western C entral E urope based on multiscale observations - Yongshuo H. Fu; Shilong Piao; Maarten Op de Beeck; Nan Cong; Hongfang Zhao; Yuan Zhang; Annette Menzel; Ivan A. Janssens (Global Ecology and Biogeography, 2014)
Aim Although numerous studies have reported advanced N orthern H emisphere spring phenology since the 1980s, recent studies based on remote sensing have reported a reversal or deceleration of this trend. This study aimed (1) to fully understand recent spring phenology shifts using both in situ observations and satellite‐based normalized difference vegetation index ( NDVI ) datasets, and (2) to test whether the NDVI methods capture the trends observed in situ. Location W estern C entral E urope. Methods Temporal spring phenology trends (leaf unfolding dates) were examined using 1,001,678 in situ observations of 31 plant species at 3984 stations, as well as NDVI ‐based start‐of‐season dates, obtained using five different methods, across the pixels that included the phenology stations. Results In situ and NDVI observations both indicated that spring phenology significantly advanced during the period 1982–2011 at an average rate of −0.45 days yr −1 . This trend was not uniform across the period and significantly weakened over the period 2000–2011. Furthermore, opposite trends were found between in situ and NDVI observations over the period 2000–2011. Averaged over all species, the in situ observations indicated a slower but still advancing trend for leaf unfolding, whereas the NDVI series showed a delayed spring phenology. Main conclusions The recent trend reversal in the advancement of spring phenology in western C entral E urope is likely to be related to the response of early spring species to the cooling trend in late winter. In contrast, late spring species continued to exhibit advanced leaf unfolding, which is consistent with the warming trend during spring months. Because remote sensing does not distinguish between species, the signal of growing‐season onset may only reflect the phenological dynamics of these earliest species in the pixel, even though most species still exhibit advancing trends.

Inter-Grade and Inter-Batch Variability of Sodium Alginate Used in Alginate-Based Matrix Tablets - Shao Fu; Ira S. Buckner; Lawrence H. Block (AAPS PharmSciTech, 2014)

Oncogenic and tumor suppressive roles of microRNAs in apoptosis and autophagy - Y. Chen; L. L. Fu; X. Wen; B. Liu; J. Huang; J. H. Wang; Y. Q. Wei (Apoptosis, 2014)

Prevalence of carbapenem-hydrolyzing class D β-lactamase genes in Acinetobacter spp. isolates in China - S. Ji; Y. Chen; Z. Ruan; Y. Fu; J. Ji; Y. Fu; H. Wang; Y. Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Influence of outbreak of macroalgal blooms on phosphorus release from the sediments in Swan Lake Wetland, China - L. Gao; Q. Wei; F. Fu; H. Shao (Plant Biosystems, 2013)

Study on elastic P-wave propagation law in unfavorable geologic structures with discontinuous deformation analysis method - Y. H. Zhang; X. D. Fu; Q. Sheng; X. L. Leng (Arabian Journal of Geosciences, 2013)

A Factorial-based Dynamic Analysis Method for Reservoir Operation Under Fuzzy-stochastic Uncertainties - D. Z. Fu; Y. P. Li; G. H. Huang (Water Resources Management, 2013)

Superparamagnetic Iron Oxide is Suitable to Label Tendon Stem Cells and Track Them In Vivo with MR Imaging - Yunfa Yang; Jianying Zhang; Yongxian Qian; Shiwu Dong; He Huang; Fernando E. Boada; Freddie H. Fu; James H-C. Wang (Annals of Biomedical Engineering, 2013)

Scanning Electron Microscopy Studies of the Antennal Sensilla of Metaphycus parasaissetiae Zhang & Huang (Hymenoptera: Encyrtidae) - H Zhou; W J Wu; F P Zhang; Y G Fu (Neotropical Entomology, 2013)

Three genetic systems controlling growth, development and productivity of rice (Oryza sativa L.): a reevaluation of the ‘Green Revolution’ - Fan Zhang; Yun-Zhu Jiang; Si-Bin Yu; J. Ali; A. H. Paterson; G. S. Khush; Jian-Long Xu; Yong-Ming Gao; Bin-Ying Fu; R. Lafitte; Zhi-Kang Li (Theoretical and Applied Genetics, 2013)

Scl gene construction, expression and effect on hemangioma - H. X. Yin; Z. H. Zhang; J. C. Shen; A. L. Zhang; T. Y. Zhang; J. X. Luo; C. Y. Fu; X. P. Yi; Z. W. Liu; S. S. Yang; B. Zhou; X. Fu (Molecular Biology Reports, 2013)

Ribonuclease 4 protects neuron degeneration by promoting angiogenesis, neurogenesis, and neuronal survival under stress - Shuping Li; Jinghao Sheng; Jamie K. Hu; Wenhao Yu; Hiroko Kishikawa; Miaofen G. Hu; Kaori Shima; David Wu; Zhengping Xu; Winnie Xin; Katherine B. Sims; John E. Landers; et al. (Angiogenesis, 2013)

Trichosporon vanderwaltii sp. nov., an asexual basidiomycetous yeast isolated from soil and beetles - Thabiso E. Motaung; Jacobus Albertyn; Johan L. F. Kock; Ching-Fu Lee; Sung-Oui Suh; Meredith Blackwell; Carolina H. Pohl (Antonie van Leeuwenhoek, 2013)

Arsenic accumulation and distribution in the tissues of inbred lines in maize (Zea mays L.) - Z. H. Liu; W. H. Li; H. Y. Qi; G. L. Song; D. Ding; Z. Y. Fu; J. B. Liu; J. H. Tang (Genetic Resources and Crop Evolution, 2012)

Hydrocarbon- and ore-bearing basinal fluids: a possible link between gold mineralization and hydrocarbon accumulation in the Youjiang basin, South China - X. X. Gu; Y. M. Zhang; B. H. Li; S. Y. Dong; C. J. Xue; S. H. Fu (Mineralium Deposita, 2012)

Correlation between plasma amino acid profiles and the various stages of hepatitis B infection - J. Yang; J. He; H. Cao; X. Zhao; S. Fu; H. Lu; Y. Chen; X. Pan; L. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Constitutive expression of barley α-amylase in Pichia pastoris by high-density cell culture - Z. W. Liu; H. X. Yin; X. P. Yi; A. L. Zhang; J. X. Luo; T. Y. Zhang; C. Y. Fu; Z. H. Zhang; J. C. Shen; L. P. Chen (Molecular Biology Reports, 2012)

Constraining the mid-crustal channel flow beneath the Tibetan Plateau: data from the Nielaxiongbo gneiss dome, SE Tibet - Dan-Ping Yan; Mei-Fu Zhou; Paul T. Robinson; Djordje Grujic; John Malpas; Allen Kennedy; Peter H. Reynolds (International Geology Review, 2012)

A fuzzy-Markov-chain-based analysis method for reservoir operation - D. Z. Fu; Y. P. Li; G. H. Huang (Stochastic Environmental Research and Risk Assessment, 2012)

Molecular cloning, characterization and expression analysis of B cell translocation gene 1 in grass carp Ctenopharyngodon idella - Y. J. Fu; F. G. Huang; T. Yuan; J. R. Gu; G. Q. Luo; H. Xu (Journal of Fish Biology, 2012)
An expressed sequence tag (EST) of B cell translocation gene (BTG) 1 ( gcbtg1 ) was obtained from a grass carp Ctenopharyngodon idellus intestinal complementary (c)DNA library and the full‐length cDNA sequence was acquired by rapid amplification of cDNA ends (RACE) technology. The predicted Gcbtg1 protein contains the box A and box B motifs which characterized the BTG and transducer of ERBB2 (TOB) family. Multiple alignment analysis reveals that Gcbtg1 shares an overall identity of 65–94% with Gcbtg1s of other vertebrates. Real‐time quantitative PCR analysis reveals that the highest expression level of gcbtg1 was detected in liver and the lowest in muscle. Western blotting analysis indicates that the immunological cross‐reactivity occurs between C. idella and human Homo sapiens BTG1 protein. A 1008 bp 5′‐flanking region sequence was cloned and analysed.

Association between ATM 5557G>A polymorphism and breast cancer risk: a meta-analysis - Chen Mao; Vincent C. H. Chung; Ben-Fu He; Rong-Cheng Luo; Jin-Ling Tang (Molecular Biology Reports, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Bayesian calibration of the Unified budburst model in six temperate tree species - Yongshuo H. Fu; Matteo Campioli; Gaston Demarée; Alex Deckmyn; Rafiq Hamdi; Ivan A. Janssens; Gaby Deckmyn (International Journal of Biometeorology, 2012)

Numerical simulation of fluxes generated by inhomogeneities of the underlying surface over the Jinta Oasis in Northwestern China - Wanli Li; Shihua Lü; Shenming Fu; Xianhong Meng; H. C. Nnamchi (Advances in Atmospheric Sciences, 2011)

Relevance of Rheological Properties of Sodium Alginate in Solution to Calcium Alginate Gel Properties - Shao Fu; Ankur Thacker; Diana M. Sperger; Riccardo L. Boni; Ira S. Buckner; Sachin Velankar; Eric J. Munson; Lawrence H. Block (AAPS PharmSciTech, 2011)

Differential distribution of heparan sulfate glycoforms and elevated expression of heparan sulfate biosynthetic enzyme genes in the brain of mucopolysaccharidosis IIIB mice - Douglas M. McCarty; Julianne DiRosario; Kadra Gulaid; Smruti Killedar; Arie Oosterhof; Toin H. van Kuppevelt; Paul T. Martin; Haiyan Fu (Metabolic Brain Disease, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Erratum: Rheological Evaluation of Inter-Grade and Inter-Batch Variability of Sodium Alginate - Shao Fu; Ankur Thacker; Diana M. Sperger; Riccardo L. Boni; Sachin Velankar; Eric J. Munson; Lawrence H. Block (AAPS PharmSciTech, 2011)

A new long terminal repeat (LTR) sequence allows to identify J genome from JS and St genomes of Thinopyrum intermedium - Z. X. Tang; Z. J. Yang; S. L. Fu; M. Y. Yang; G. R. Li; H. Q. Zhang; F. Q. Tan; Zhenglong Ren (Journal of Applied Genetics, 2011)

Mechanisms for phenotypic variation in Lesch–Nyhan disease and its variants - Radhika Sampat; Rong Fu; Laura E. Larovere; Rosa J. Torres; Irene Ceballos-Picot; Michel Fischbach; Raquel de Kremer; David J. Schretlen; Juan Garcia Puig; H. A. Jinnah (Human Genetics, 2011)

Rheological Evaluation of Inter-grade and Inter-batch Variability of Sodium Alginate - Shao Fu; Ankur Thacker; Diana M. Sperger; Riccardo L. Boni; Sachin Velankar; Eric J. Munson; Lawrence H. Block (AAPS PharmSciTech, 2010)

Inter- and Intra-Manufacturer Variability in Pharmaceutical Grades and Lots of Xanthan Gum - Ankur Thacker; Shao Fu; Riccardo L. Boni; Lawrence H. Block (AAPS PharmSciTech, 2010)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

Molecular characterization and association analysis of FBXO40 with partial hematological indexes in pig - Z. W. Wang; X. Y. Li; Z. L. Tang; S. L. Yang; Z. Z. Ying; T. Fu; B. Fan; Y. L. Mu; H. Ao; K. Li (Molecular Biology Reports, 2010)

OSTM/Jason-2: Assessment of the System Performances (Ocean Surface Topography Mission: OSTM) - G. Zaouche; J. Perbos; T. Lafon; V. Couderc; J. Lambin; J. D. Desjonqueres; C. Jayles; E. Jurado; P. Vaze; L.-L. Fu; S. Brown; F. Parisot; et al. (Marine Geodesy, 2010)

Simultaneous determination of residues of trichlorfon and dichlorvos in animal tissues by LC-MS/MS - G.M. Wang; H. Dai; Y.G. Li; X.L. Li; J.Z. Zhang; L. Zhang; Y.Y. Fu; Z.G. Li (Food Additives & Contaminants: Part A, 2010)

QTL detection for grain oil and starch content and their associations in two connected F2:3 populations in high-oil maize - Y. Z. Wang; J. Z. Li; Y. L. Li; M. G. Wei; X. H. Li; J. F. Fu (Euphytica, 2010)

Transfer to wheat (Triticum aestivum) of small chromosome segments from rye (Secale cereale) carrying disease resistance genes - S. Fu; Z. Tang; Z. Ren; H. Zhang (Journal of Applied Genetics, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

An improved nitrogen difference method for estimating biological nitrogen fixation in legume-based intercropping systems - Chang-Bing Yu; Yu-Ying Li; Chun-Jie Li; Jian-Hao Sun; X. H. He; Fu-Suo Zhang; Long Li (Biology and Fertility of Soils, 2010)

Nucleotide diversity and molecular evolution of the PSY1 gene in Zea mays compared to some other grass species - Zhiyuan Fu; Jianbing Yan; Yanping Zheng; Marilyn L. Warburton; Jonathan H. Crouch; Jian-Sheng Li (Theoretical and Applied Genetics, 2010)

Vertical Distribution of Polybrominated Diphenyl Ethers (PBDEs) in Soil Cores Taken from a Typical Electronic Waste Polluted Area in South China - Z. Z. Yang; Y. F. Li; Y. X. Hou; H. Y. Liang; Z. F. Qin; S. Fu (Bulletin of Environmental Contamination and Toxicology, 2010)

Tissue Distribution of Polybrominated Diphenyl Ethers (PBDEs) in Captive Domestic Pigs, Sus scrofa, from a Village Near an Electronic Waste Recycling Site in South China - Y. F. Li; Z. Z. Yang; C. H. Wang; Z. J. Yang; Z. F. Qin; S. Fu (Bulletin of Environmental Contamination and Toxicology, 2010)

Bats aloft: variability in echolocation call structure at high altitudes - Erin H. Gillam; Gary F. McCracken; John K. Westbrook; Ya-Fu Lee; Michael L. Jensen; Ben B. Balsley (Behavioral Ecology and Sociobiology, 2009)

Effect of polymorphism in the leukemia inhibitory factor gene on litter size in Large White pigs - H. C. Lin; G. F. Liu; A. G. Wang; L. J. Kong; X. F. Wang; J. L. Fu (Molecular Biology Reports, 2009)

Dent corn genetic background influences QTL detection for grain yield and yield components in high-oil maize - Y. L. Li; X. H. Li; J. Z. Li; J. F. Fu; Y. Z. Wang; M. G. Wei (Euphytica, 2009)

Polybrominated Diphenyl Ethers in Mudsnails (Cipangopaludina cahayensis) and Sediments from an Electronic Waste Recycling Region in South China - Z. Z. Yang; X. R. Zhao; Z. F. Qin; S. Fu; X. H. Li; X. F. Qin; X. B. Xu; Z. X. Jin (Bulletin of Environmental Contamination and Toxicology, 2009)

Composition, Distribution, and Characterization of Polycyclic Aromatic Hydrocarbons in Soil in Linfen, China - S. Fu; H. X. Cheng; Y. H. Liu; X. J. Xia; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

An empirical approach to retrieving monthly evapotranspiration over Amazonia - Negrón R. I. Juárez; M. L. Goulden; R. B. Myneni; R. Fu; S. Bernardes; H. Gao (International Journal of Remote Sensing, 2008)

Organochlorine Pesticides in the Soil in Linfen, China - H. X. Cheng; S. Fu; Y. H. Liu; D. S. Li; J. H. Zhou; X. J. Xia (Bulletin of Environmental Contamination and Toxicology, 2008)

Polychlorinated Biphenyls Residues in the Soil in Linfen, China - S. Fu; H. Cheng; Y. Liu; L. Zhang; Z. Yang; K. Li; X. Xia; X. Xu (Bulletin of Environmental Contamination and Toxicology, 2008)

Predictability of South American low‐level jet using QuikSCAT ocean surface wind - H. Wang; R. Fu; J. K. Schemm; W. Tang; W. T. Liu (International Journal of Remote Sensing, 2008)

Production of a new wheat cultivar with a different 1B.1R translocation with resistance to powdery mildew and stripe rust - Z. Tang; S. Fu; Z. Ren; H. Zhang; Z. Yang; B. Yan; H. Zhang (Cereal Research Communications, 2008)

Two new flavanes and bioactive compounds from Daphne tangutica Maxim - W. Zhang; Y. H. Shen; Z. Y. Lou; R. H. Liu; C. Zhang; P. Fu; L. Shan; W. D. Zhang (Natural Product Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Molecular characterization of the surface glycoprotein genes of an H5N1 influenza virus isolated from a human in Guangdong, China - J.-J. Zhou; J. Fu; D.-Y. Fang; H.-J. Yan; J. Tian; J.-M. Zhou; J.-P. Tao; Y. Liang; L.-F. Jiang (Archives of Virology, 2007)

Modulation of neural response to happy and sad faces by acute tryptophan depletion - Paolo Fusar-Poli; Paul Allen; Francis Lee; Simon Surguladze; Nigel Tunstall; Cynthia H. Y. Fu; Michael J. Brammer; Anthony J. Cleare; Philip K. McGuire (Psychopharmacology, 2007)

Overexpression of barley hva1 gene in creeping bentgrass for improving drought tolerance - Daolin Fu; Bingru Huang; Yanmei Xiao; Subbaratnam Muthukrishnan; George H. Liang (Plant Cell Reports, 2007)

Sesquiterpene lactones from Saussurea alata - G. Ren; Z. M. Yu; Y. L. Chen; S. H. Wu; C. X. Fu (Natural Product Research, 2007)

Octad pollen formation in Cymbopetalum (Annonaceae): the binding mechanism - C. -H. Tsou; Y. -L. Fu (Plant Systematics and Evolution, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Two new xanthones from Hypericum japonicum - P. Fu; W.-D. Zhang; R. H. Liu; T.-Z. Li; Y.-H. Shen; H.-L. Li; W. Zhang; H.-S. Chen (Natural Product Research, 2006)

Geochemical evidence for the variation of historical seabird population on Dongdao Island of the South China Sea - X. D. Liu; S. P. Zhao; L. G. Sun; H. H. Luo; X. B. Yin; Z. Q. Xie; Y. H. Wang; K. X. Liu; X. H. Wu; X. F. Ding; D. P. Fu (Journal of Paleolimnology, 2006)

Effect of acute tryptophan depletion on pre-frontal engagement - Paul P. Allen; Anthony J. Cleare; Francis Lee; Paolo Fusar-Poli; Nigel Tunstall; Cynthia H. Y. Fu; Micheal J. Brammer; Philip K. McGuire (Psychopharmacology, 2006)

Effect of specific inspiratory muscle warm-up on intense intermittent run to exhaustion - Tom K. Tong; Frank H. Fu (European Journal of Applied Physiology, 2006)

Phthalate Ester Pollution in Urban Soil of Beijing, People's Republic of China - X. H. Li; L. L. Ma; X. F. Liu; S. Fu; H. X. Cheng; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2006)

Genetic analyses and mapping of a new thermo-sensitive genic male sterile gene in maize - J. H. Tang; Z. Y. Fu; Y. M. Hu; J. S. Li; L. L. Sun; H. Q. Ji (Theoretical and Applied Genetics, 2006)

Seasonal Variation of the Particle Size Distribution of n-Alkanes and Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Aerosol of Guangzhou, China - X. L. Tang; X. H. Bi; G. Y. Sheng; J. H. Tan; J. M. FU (Environmental Monitoring and Assessment, 2006)

Complete nucleotide sequences and genome characterization of double-stranded RNA 1 and RNA 2 in the Raphanus sativus-root cv. Yipinghong - L. Chen; J. S. Chen; L. Liu; X. Yu; S. Yu; T. Z. Fu; W. H. Liu (Archives of Virology, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

A Modified Cyclic Cracking Model for RC Structural Walls Behaviour Under Dynamic Excitation - Tsai-Fu Chuang; Andrew H. C. Chan; Les A. Clark (Bulletin of Earthquake Engineering, 2005)

QTLs for drought escape and tolerance identified in a set of random introgression lines of rice - J. L. Xu; H. R. Lafitte; Y. M. Gao; B. Y. Fu; R. Torres; Z. K. Li (Theoretical and Applied Genetics, 2005)

Effects of ketamine on prefrontal and striatal regions in an overt verbal fluency task: a functional magnetic resonance imaging study - Cynthia H. Y. Fu; Kathryn M. Abel; Matthew P. G. Allin; David Gasston; Sergi G. Costafreda; John Suckling; Steve C. R. Williams; Philip K. McGuire (Psychopharmacology, 2005)

Sleep-related vagotonic effect of zolpidem in rats - Hsiao Ying Chen; Terry B. J. Kuo; Fu-Zen Shaw; Ching J. Lai; Cheryl C. H. Yang (Psychopharmacology, 2005)

Genome-wide Introgression Lines and their Use in Genetic and Molecular Dissection of Complex Phenotypes in Rice (Oryza sativa L.) - Zhi-Kang Li; Bin-Ying Fu; Yong-Ming Gao; Jian-Long Xu; J. Ali; H. R. Lafitte; Yun-Zhu Jiang; J. Domingo Rey; C. H. M. Vijayakumar; R. Maghirang; Tian-Qing Zheng; Ling-Hua Zhu (Plant Molecular Biology, 2005)

Tryptophan depletion reduces right inferior prefrontal activation during response inhibition in fast, event-related fMRI - Katya Rubia; Francis Lee; Anthony J. Cleare; Nigel Tunstall; Cynthia H. Y. Fu; Michael Brammer; Phillip McGuire (Psychopharmacology, 2005)

Simulation Studies of High-Latitude Magnetospheric Boundary Dynamics - Q. Q. Shi; Z. Y. Pu; H. Zhang; S. Y. Fu; C. J. Xiao; Q. -G. Zong; T. A. Fritz; Z. X. Liu (Surveys in Geophysics, 2005)

Energetic Particles Observed in the CUSP Region During a Storm Recovery Phase - S. Y. Fu; Q. G. Zong; Z. Y. Pu; C. J. Xiao; A. Korth; P. Daly; H. Reme (Surveys in Geophysics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

GISH, AFLP and PCR-RFLP analysis of an intergeneric somatic hybrid combining Goutou sour orange and Poncirus trifoliata - C. H. Fu; C. L. Chen; W. W. Guo; X. X. Deng (Plant Cell Reports, 2004)

Amazonian climate: results and future research - J. H. C. Gash; C. Huntingford; J. A. Marengo; R. A. Betts; P. M. Cox; G. Fisch; R. Fu; A. W. Gandu; P. P. Harris; L. A. T. Machado; C. von Randow; M. A. Silva Dias (Theoretical and Applied Climatology, 2004)

Segmental nerve conduction velocity in vibration-exposed shipyard workers - M. Cherniack; A. J. Brammer; R. Lundstrom; J. Meyer; T. F. Morse; G. Nealy; T. Nilsson; D. Peterson; E. Toppilla; N. Warren; R. W. Fu; H. Bruneau (International Archives of Occupational and Environmental Health, 2004)

Molecular diversity and multilocus organization of the parental lines used in the International Rice Molecular Breeding Program - S. B. Yu; W. J. Xu; C. H. M. Vijayakumar; J. Ali; B. Y. Fu; J. L. Xu; Y. Z. Jiang; R. Marghirang; J. Domingo; C. Aquino; S. S. Virmani; Z. K. Li (Theoretical and Applied Genetics, 2003)

Regeneration of citrus sinensis (+) clausena lansium intergeneric triploid and tetraploid somatic hybrids and their identification by molecular markers - C. H. Fu; W. W. Guo; J. H. Liu; X. X. Deng (In Vitro Cellular & Developmental Biology - Plant, 2003)

Acute and moderate-term creatine monohydrate supplementation does not affect creatine transporter mRNA or protein content in either young or elderly humans - Mark Tarnopolsky; Gianni Parise; Min-H Fu Surname; Andrea Brose; Andrew Prasad; Oliver Speer; Theo Wallimann (Molecular and Cellular Biochemistry, 2003)

Distribution of Organochlorine Pesticides in a Sediment Profile of the Pearl River Estuary - X. D. Li; B. X. Mai; G. Zhang; G. Y. Sheng; J. M. Fu; S. M. Pan; O. W. H. Wai; Y. S. Li (Bulletin of Environmental Contamination and Toxicology, 2001)

Attenuated Lapinized Chinese Strain of Classical Swine Fever Virus: Complete Nucleotide Sequence and Character of 3′-Noncoding Region - H. X. Wu; J. F. Wang; C. Y. Zhang; L. Z. Fu; Z. S. Pan; N. Wang; P. W. Zhang; W. G. Zhao (Virus Genes, 2001)

CDK inhibitors suppress apoptosis induced by chemicals and by excessive expression of a cell death gene, reaper, in Drosophila cells - M. Nagano; K. Ui-Tei; H. Suzuki; Zheng-fu Piao; Y. Miyata (Apoptosis, 2000)

Genetic susceptibility to pre-eclampsia and chromosome 7q36 - G. Guo; J.A. Lade; A.N. Wilton; E.K. Moses; M. Grehan; Y. Fu; H. Qiu; D.W. Cooper; S.P. Brennecke (Human Genetics, 1999)

Genetic susceptibility to pre-eclampsia and chromosome 7q36 - G. Guo; J.A. Lade; A.N. Wilton; E.K. Moses; M. Grehan; Y. Fu; H. Qiu; D.W. Cooper; S.P. Brennecke (Human Genetics, 1999)

Functional analysis of the proteasome regulatory particle - Michael H. Glickman; David M. Rubin; Hongyong Fu; Christopher N. Larsen; Olivier Coux; Inge Wefes; Günter Pfeifer; Zdenka Cjeka; Richard Vierstra; Wolfgang Baumeister; Victor Fried; Daniel Finley (Molecular Biology Reports, 1999)

Structure and functional analyses of the 26S proteasome subunits from plants – Plant 26S proteasome - Hongyong Fu; Pierre-Alain Girod; Jed H. Doelling; Steven van Nocker; Mark Hochstrasser; Daniel Finley; Richard D. Vierstra (Molecular Biology Reports, 1999)

The barriers to bluetongue virus infection, dissemination and transmission in the vector, Culicoides variipennis (Diptera: Ceratopogonidae) - H. Fu; C. J. Leake; P. P. C. Mertens; P. S. Mellor (Archives of Virology, 1999)

Studies on somaclonal variation in Phalaenopsis - W. H. Chen; T. M. Chen; Y. M. Fu; R. M. Hsieh; W. S. Chen (Plant Cell Reports, 1998)

Use of alternate splice sites in granule-bound starch synthase mRNA from low-amylose rice varieties - H. Frances J. Bligh; Patrick D. Larkin; Paul S. Roach; Christopher A. Jones; Hongyong Fu; William D. Park (Plant Molecular Biology, 1998)

Anchor probes for comparative mapping of grass genera - A. E. Van Deynze; M. E. Sorrells; W. D. Park; N. M. Ayres; H. Fu; S. W. Cartinhour; E. Paul; S. R. McCouch (Theoretical and Applied Genetics, 1998)

Angiotensin II receptors: Localization of type I and type II in rat epididymides of different developmental stages - P. S. Leung; H. C. Chan; L. X. M. Fu; P. Y. Leung; S. B. C. Chew; P. Y. D. Wong (The Journal of Membrane Biology, 1997)

Comparative Analyses of Soil Contaminant Levels and Plant Species Diversity at Developing and Disused Oil Well Sites in Qianjiang Oilfield, China - Z.-T. Xiong; H.-X. Hu; Y.-X. Wang; G.-H. Fu; Z.-Q. Tan; G.-A. Yan (Bulletin of Environmental Contamination and Toxicology, 1997)

A model for interpreting the tracer labeling of interendothelial clefts - Bingmei Fu; Fitz-Roy E. Curry; Roger H. Adamson; Sheldon Weinbaum (Annals of Biomedical Engineering, 1997)

Determination of thein situ forces and force distribution within the human anterior cruciate ligament - Glen A. Livesay; Hiromichi Fujie; Shinji Kashiwaguchi; Duane A. Morrow; Freddie H. Fu; Savio L. -Y. Woo (Annals of Biomedical Engineering, 1995)

A one-year survey of rotavirus strains from three locations in Bangladesh - Leanne E. Unicomb; Fu Bingnan; Z. Rahim; N. N. Banu; J. G. Gomes; G. Podder; M. H. Munshi; S. R. Tzipori (Archives of Virology, 1993)

Effect of waterborne and dietary cadmium on plasma ions of the teleostOreochromis mossambicus in relation to water calcium levels - H. B. Pratap; H. Fu; R. A. C. Lock; S. E. Wendelaar Bonga (Archives of Environmental Contamination and Toxicology, 1989)